Hepatocyte growth factor-overexpressing bone marrow stem cells relieve incision-induced postoperative pain - Chong-Jun Xu; Xiao-Yun Cai; He-Fan He; Zhi-Yuan Chen; Hong-Geng Wang; Wei-Feng Liu; Hai-Ping You (Tissue and Cell, 2027)

Seasonal drivers of picoeukaryotic community structure and assembly in complex aquatic systems: A case study of the Changjiang (Yangtze) River Estuary and East China Sea - Ran Li; Wenxin Fan; Xianghui Guo; Yan Bai; Ping Sun; Nianzhi Jiao; Dapeng Xu (Marine Pollution Bulletin, 2026)

Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

Linear and nonlinear viscoelastic behavior of novel Sanxan/Poly(γ-glutamic acid) gels: Thermal and rheological insights - Xue Zhang; Baoping Wang; Yue Wang; Ping Cheng; Jun Han; Fang Tian; Zhiping Fan (Food Hydrocolloids, 2026)

Correction: Rab11-FIP4 interacts with ARF5 to promote cancer stemness in hepatocellular carcinoma - Feifeng Song; Qi Zhang; Xixuan Lu; Tong Xu; Qing Hu; Xiaoping Hu; Weijiao Fan; Yiwen Zhang; Ping Huang (Journal of Physiology and Biochemistry, 2026)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

STEAP3 regulates ferroptosis through mitochondrial metabolic dysfunction to impact the malignant proliferation of ovarian cancer cells - Wenhua Liang; Xingyan Liu; Yan Wei; Xuran Liu; Zhiwei Fan; Panpan Yu; Ping Yang (Functional & Integrative Genomics, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Reshaping microbial function through Blastobotrys adeninivorans bioaugmentation to enhance flavor quality in ripened pu-erh tea: Insights from multi-omics analysis - Teng Wang; Yan Ma; Qiuyue Chen; Nianguo Bo; Guangqiang Wei; Yanhui Guan; Yiqing Guan; Dihan Yang; Hongyan Gao; Fan Yang; Xiaying Tao; Ping Liang; et al. (International Journal of Food Microbiology, 2026)

Oleogel fabrication from Lactobacillus-stabilized emulsion templates: The role of bacterial surface properties in network stabilization mechanisms - Xiaoyi Jiang; Ping Yin; Ying Wang; Jian Ding; Fengjiao Fan; Yong Fang (Food Research International, 2026)

Integrated electronic nose, GC–MS, and metagenomic analyses reveal volatile flavor and microbial community differences in heap-fermented grains of Jiangxiangxing Baijiu across different fermentation degrees - Guiyin Li; Lixia Shen; Lei Nie; Ping Tang; Qimuge Shan; Liqin Qin; Shuangxi Fan; Xuewu Guo (Food Research International, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Self-assembled zein-chitosan-salicylic acid nanoemulsions delay mango senescence by modulating hormone signaling and redox-related transcriptional networks - Yiting Fan; Muhammad Adil; Jiahao Ren; Youning Zou; Tai Boon Tan; Chin Ping Tan; Fengsong Liu; Xinglong Xiao (Food Hydrocolloids, 2026)

Functions of tandem-repeat galectins and domain coordination governs galectin-4 activity in grass carp (Ctenopharyngodon idella) - Hongzhou Xu; Tian Yang; Haixia Liu; Huanjie Li; Ping Cheng; Yuxin Shen; Di Wang; Zijun Fan; Heyi Liu (Fish & Shellfish Immunology, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Tuning the signal-to-noise ratio: An electrokinetic strategy for high-fidelity SERS biosensing of microRNA-21 - Kangzhe Cao; Fan Zhang; Jiakun Zhang; Jinjin Fu; Ping Lu; Jun-Tao Cao; Huiqiao Liu (Analytica Chimica Acta, 2026)

Government subsidy strategy and ship green upgrading decision in coal water transportation - Xiang Li; Xiaoqian Ma; Zhong Du; Changan Li; Zhi-Ping Fan (Ocean & Coastal Management, 2026)

Ultra-high Phosphogypsum road base: Mix proportion design, microscopic mechanism, heavy metal leaching law and carbon reduction - Si-fan Meng; Chao-qiang Wang; Nan Li; Li-ping Zheng (Sustainable Chemistry and Pharmacy, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Dataset Construction of CO2 Flux over Shifting Sand in the Taklimakan Desert and Assessment of Carbon Sequestration Capacity - Ping Yang; Jianping Huang; Fan Yang; Xinqian Zheng; Jiacheng Gao; Meiqi Song; Mingjie Ma; Ali Mamtimin; Chenglong Zhou; Wen Huo; Xinghua Yang; Qingfan Song; et al. (Advances in Atmospheric Sciences, 2026)

Isoprenylated phenolic derivatives from Corethrodendron scoparium and their anti-triple negative breast cancer activity - Yuan Gao; Ping Hai; Hai-Yan Jia; Mei-Ling Yang; Hui-Xia Fan; Jin Yang; Xian-Yan Li; Lian Yang; Zhi-Qiang Luo; Jian Yang (Phytochemistry, 2026)

A comparative evaluation of static and dynamic test methods for assessing the effectiveness of biopolymer-based dust suppressants in mine tailings - Weifan Wu; Ping Chang; Apurna Ghosh; Bowen Fan; Ramakrishna Morla (Minerals Engineering, 2026)

Improving the efficiency of a bioaerosol disinfection reactor by using ultraviolet C light-emitting diodes and titanium dioxide photocatalyst - Chien-Ping Wang; Bo Yu Liao; Fan-Chun Hsieh; Qiang Jia; Tien-Li Chang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Season- and phase-associated variation in the molecular composition and redox–photochemical reactivity of dissolved organic matter at paired river and lake sites - Xufang Yu; Nennen Zhu; Limeng Shao; Yichun Wang; Wenchao Ji; Cuncun Xu; Tao Cao; Jianzhong Song; Xingjun Fan; Ping’an Peng (Journal of Hazardous Materials, 2026)

Effect of depth-direction SVF gradient on particle deposition performance in fibrous media - Ankang Zhou; Shihang Li; Jiahua Chai; Kunkun Tu; Hao Jin; Wenjie Liang; Shuda Hu; Fan Geng; Qiang Zhang; Wuping Peng; Ping Li (Journal of Aerosol Science, 2026)

Volatile organic compounds, nutritional content, and antioxidant activities of morel mushrooms: Effects of different cooking treatments - Fuyan Li; Qian Zhang; Yufeng Qin; Yongyu Guo; Ping Shao; Lei Guo; Qian Ma; Fangyu Fan (International Journal of Gastronomy and Food Science, 2026)

MOSP: A Multi-Orientation Sequential Picking Planning for Robotic Harvest of Breeding Cotton - Jiawei Fan; Guohang Lu; Nianzu Dai; Xuemei Liu; Ping Zhang; Jin Yuan (Computers and Electronics in Agriculture, 2026)

Evaluation and analysis of the efficacy of four Chinese herbal medicines and formulations in preventing and treating Mycoplasma gallisepticum infection in chickens - Yongfeng Yan; Lvyan Liao; Yutao Fan; Ping Liu; Xiaoping Wu; Yijian Wu (The Veterinary Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Tectonic forcing and climate modulation on the evolution of aeolian sediment provenance from the northeastern Tibetan Plateau margin to the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Chuanying Zhu; Xueyu Yan; Ke Bi; Qiang Shu; Ping Zhang (Quaternary Science Reviews, 2026)

A peroxisomal metabolic route from benzoyl-CoA to benzyl alcohol for phenylalanine-derived salicylic acid biosynthesis in rice - Yukang Wang; Shuyan Song; Wenxuan Zhang; Qianwen Deng; Yang Lai; Zhixue Huo; Shanshan Li; Qi Zhang; Yuchen Ping; Jiarong Chen; Zeng Tao; Yanlei Feng; et al. (Molecular Plant, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

Atmospheric versus soil Cadmium exposure in rice (Oryza sativa L.): Divergent toxicological mechanisms and human health risks via integrated multi-omics - Xiaoxue Ouyang; Jie Ma; Zheng Pan; Rongfei Wei; Qiusheng Chen; Fan Su; Ping Yin; Ziyun Liu; Zhen Wang; Cuiyun Niu; Shuchang Lu; Qiang Zhang; et al. (Journal of Hazardous Materials, 2026)

Investigating the saltiness enhancement in blanch-pretreated celery juice via odor-taste cross-modal integration: insights from EEG, molecular simulations, and flavoromics - Aiqi Zhang; Ping Zhan; Wanying He; Guangsen Fan; Jingzhang Geng; Chunmei Gou; Liang Tian; Peng Wang; Honglei Tian (Food Chemistry, 2026)

A Copula-based Dynamic Bayesian Network for analyzing spatiotemporal runoff encounter patterns in water source areas of inter-basin water transfer project - Juan Chen; Ke Li; Yi-fan Liang; Ping-an Zhong (Environmental Research, 2026)

Wind Stress and Wind Disturbance Control Litterfall and Carbon Flux - Chen-Chia Ku; Sin Chen; Cheng-Yu Wu; Chun-Ping Huang; Bing-Mu Hsu; James A. Lutz; Wei-Chun Chao; Cheng-Wei Fan (Ecosystems, 2026)

A novel framework for generalized potential slip surfaces in complex slopes using polar angle incrementation - Dong-ping Deng; Run-dong Xu; Yi-hang Peng; Chao-fan Zhu (Landslides, 2026)

Transcriptomic analysis of lncRNA-miRNA-mRNA competing endogenous RNA regulatory networks in radiation-induced mouse thymic degeneration - Fei Wang; Qing-hua Yu; Xin-ming Fan; Cun-yang Guo; Si-guang Xu; Wen-bo Zhang; Ping Xu (Immunologic Research, 2026)

Phytochemicals from the leaves of Staphylea arguta (Turpiniae Folium) and their anti-inflammatory activity - Shumin Wu; Feifei Tang; Xiyu Xu; Xiaoxiang Fan; Danting Luo; Yunqing He; Ping Hai; Shengxiang Yang; Yuan Gao; Jian Yang (Natural Product Research, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Plant-specific groundwater source apportionment and health risk assessment of chemical industrial parks based on an enhanced potential pollution index framework - Junjie Li; Jingjing Yu; Bin Yang; Ping Du; Chunmei Han; Juan Chen; Bei Yuan; Yunhui Zhang; Ruibing Han; Wenxuan Fan (Journal of Hazardous Materials, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

Predictable toxicity of antibiotics and disinfection by-products as well as their mixtures based on the mechanism-oriented analysis - Guang-zhen Ji; Jing Zhang; Yuan-fan Zhao; Shu-guang Zhu; Ren-yong Jia; Jian-ping Zeng; Hui-yan Shen; Jin Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Phase evolution matters: How Fe(II) reshapes coprecipitate surfaces for enhanced U(VI) adsorption - Chaofei Zhang; Yuan Chen; Huiyang Mei; Weichao Zhang; Beihang Zhang; Wentao Zhang; Ping Li; Zhenying Lv; Jianjun Liang; Qiaohui Fan (Water Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Formation process of Fe-Mn Co-precipitates and Its implications for U(VI) immobilization: Mechanisms and environmental factors - Zhenying Lv; Huiyang Mei; Beihang Zhang; Weichao Zhang; Ping Li; Chaofei Zhang; Jianjun Liang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Genome-wide identification of methylation markers associated with Streptococcus agalactiae resistance in cfDNA of GIFT tilapia - Ji Ping Jiao; Tao Fei Qiao; Meng Fan Dong; Zong Xian Zhu; Jin Min Pan; Jun Hong Xia (Fish & Shellfish Immunology, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Tailored pore engineering in crystalline COF membranes via trimesoyl chloride cross-linking for high-performance pharmaceutical nanofiltration in water treatment - Hao Wang; Lian You; Jian-wei Jia; Yi Wang; Li-ping Yue; Fan-xin Kong (Chemical Engineering Journal, 2026)

Global evaluation and uncertainty analysis of MODIS Deep Blue and MAIAC aerosol products over bright surfaces - Ping Zhang; Leiku Yang; Xin Pei; Muhammad Bilal; Yuxuan Wang; Yizhe Fan; Xiaoran Lv; Xiaoxia Xue; Weiqian Ji; Xiaofeng Lu; Xiaoqian Cheng (Atmospheric Environment, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Meyerozyma caribbica NJC41 degrades aflatoxin B1 into the non-toxic aflatoxin P1 and inhibits Aspergillus flavus proliferation in kiwifruit - Xin-Chi Shi; Jin-Yan Ma; Fan Liu; Yan-Ping Ji; Ying Cao; Lei Chen; Yong-Hui Jiang; Su-Yan Wang; Su-Qin Zhu; Xin Chen; Xu-Chu Duan; Jie Gong; et al. (Food Research International, 2026)

Shaking promotes the accumulation of flavor-imparting metabolites and enhances the sensory quality of spring black tea - Chunyan Fang; Rui You; Yiyun Gong; Ping Huang; Fan Huang; Wanjun Gao; Xianlin Ye; Yulong Ye (Food Chemistry, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

Layer-tuned polypropylene mesh as a cost-effective diaphragm for stable and high-efficiency electrochemical hardness removal - Meng-Meng Wang; Xiao-Yang Luo; Fa-Guo Chong; Peng-Jun Fan; Chao Zhang; Guang-Ping Zha; Wen-Fang Cai; Qing-Yun Chen; Yun-Hai Wang (Desalination, 2026)

A critical review on abiotic geologic hydrogen generation: Mechanisms and controls - Qingxia Zheng; Ruibo Wu; Ping Li; Zhe Ding; Wentao Zhang; Huiyang Mei; Weichao Zhang; Jianjun Liang; Qiaohui Fan (Earth-Science Reviews, 2026)

Molecule engineering-driven sustainable and high-performance ionic liquids lubricant on the titanium alloy surfaces and their interfacial mechanisms - Gaolu Fan; Jingyu Shan; Jingwen Guan; Ke Yang; Hongxin He; Shibo Liu; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2026)

An ROS-scavenging dual-network hydrogel for diabetic bone regeneration - Zhengyu Cai; Weizhe Xu; Qingxiang Zhang; Xingwu Zhou; Jiang Zeng; Zhiyong Wang; Peng Deng; Ping Sun; Fan Tang; Xing Jiang; Moyuan Qu; Qianming Chen (Chemical Engineering Journal, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Quantifying the decoupling of pollution magnitude and geochemical signatures in livestock manure: a novel geometric fingerprint approach - Qiu Cheng; Yi Jijun; Fan Shoubo; Du Qiuxiang; Li Qianglin; Wang Liting; Liang Qingling; Zheng Guihua; Xiong Ping (Environmental Monitoring and Assessment, 2026)

Sediment transport mechanisms in sediment-starved subaqueous deltas: insights from storm-induced gravity flows - Chunye Hu; Fan Zhang; Jin Li; Xiaolei Liu; Fei Xing; Renzhi Li; Hao Wu; Heyu Yu; Ya Ping Wang (Journal of Hydrology, 2026)

Occurrence, ecological risk, and human health assessment of herbicide residues in Chaohu Lake, China - Yong-mei Zhang; Ping-ping Fan; Ling-zhi Zhang; Wei Yu; Song Xia; Fa-li Liu; Xue-de Li (Journal of Environmental Chemical Engineering, 2026)

Development of controlled-release potassium ferrate tablets for efficient removal of trichloroethylene in water: Kinetics and removal performance - Chia-Hung Chen; Wu-Xing Chen; Amila Kasun Abeysinghe; Po-Yen Chien; Ku-Fan Chen; Yu-Jen Shih; Wei-Hsiang Chen; Fang-Yu Liang; Yen-Ping Peng (Journal of Environmental Chemical Engineering, 2026)

Predicting distribution characteristics of PM2.5 concentrations across China combining land use regression model and spatiotemporally weighted stacking machine learning algorithms - Wentao Wang; Ping Zhang; Yuanyuan Han; Fengqian Zhang; Yue Huang; Jinbao Liu; Ying Pan; Wenping Liu; Jian Chen; Mingyao Li; Yong Wang; Yefan Jia; et al. (Journal of Environmental Chemical Engineering, 2026)

Efficient depolymerization of polystyrene waste into styrene monomers over the microwave-assisted Zn/b-ZnO catalyst system - Zijian Zhang; Bonan Liu; Li Yang; Jingwen Wang; Yuqing Dong; Chao Tang; Ping Wang; Haijiao Xie; Lei Zhang; Lu Zhang; Jun Zhao; Yu Fan; et al. (Journal of Environmental Chemical Engineering, 2026)

A case-control study linking concentrations of microplastics in human cerebrospinal fluid to intracranial aneurysm risk - Zebin Fang; Xiaoyi Wang; Fan Wu; Sihan Mao; Hao Jiang; Chi Hu; Luyuan Zhang; Weijian Fan; Chao Zhang; Ping Lan; Kaiyuan Huang; Yuxiang Weng; et al. (Environmental Pollution, 2026)

Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Probabilistic stratigraphic modeling of waste soil landfills using multiple UAV data - Shuairong Wang; Shuai Zhang; Haoquan Wang; Hui Wang; Fan Zhang; Ping Shen; Wei Yan; Wenjun Zhang; Zhuofeng Li; Liangtong Zhan (Computers and Geotechnics, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Resource utilization of spent grains, an underutilized by-product from Chinese Baijiu brewing: Recent advances and prospects - Zhao Yang; Sheng Wang; Bi Chen; Fan Yang; Ping Xiang; Li Wang; Jianlong Wang (Resources, Conservation and Recycling, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Combined effects of polystyrene micro-/nano-plastics and imidacloprid on Gut–Brain axis and neurotoxicity in juvenile Carassius auratus - Xinzi Guo; Lin Peng; Zhaoxuan Zhu; Shuocheng Fan; Jiasen Feng; Xingxing Fang; Dawei Guo; Ping Yang (Journal of Environmental Management, 2026)

Exploring the potential of calcium-chelating peptides from aquatic sources: Structure-activity relationship, computational simulation, and stability mechanism analysis - Chaozhong Fan; Xue Zhao; Zhaohui Zhang; Ping Dong; Hu Hou (Food Research International, 2026)

Thyme polyphenols modulate myofibrillar protein-odorant interactions: Molecular mechanistic insights into mutton off-flavor release - Xian Chen; Guangsen Fan; Wanying He; Peng Wang; Jingzhang Geng; Chunmei Gou; Ping Zhan; Honglei Tian (Food Chemistry, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Nanoengineering of two-dimensional materials in the baijiu brewing industry: A review - Yan Peng; Yongxin Peng; Mengjing Teng; Ying Han; Fan Yang; Ping Xiang (Food Chemistry, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Microbial taxonomic and functional responses to heavy metal gradients in mining-impacted stream sediments - Ghufran Uddin; Jiayu Song; Zhuanhong Lu; Zhang Chaofie; Wasim Sajjad; Ping Li; Qiaohui Fan (Environmental Research, 2026)

Efficient algorithms for accurately simulating radiative transfer in binary stochastic mixtures in two dimensions - Cong-Zhang Gao; Jian-Wei Yin; Ying Cai; Xu Liu; Zheng-Feng Fan; Pei Wang; Shao-Ping Zhu (Computer Physics Communications, 2026)

Flexible and anti-freezing eutectogel for high-performance ionotronic sensors - Ping Gan; Yi-Jun Cao; Ming-Ru Xie; Hui-Ping Chen; Chun-Fang Xie; Jie-Ping Fan (Chemical Engineering Journal, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

Sub-monthly features of atmospheric circulations leading to June extreme precipitation in Southwest Zhejiang Province of China - Peijun Zhu; Renguang Wu; Chengyan Mao; Jianjiang Wang; Yanan Liu; Fan Ping; Panxi Dai (Theoretical and Applied Climatology, 2026)

Semi-rational engineering of a β-farnesene synthase hybrid for enhanced production in Serratia marcescens - Wenqi Zhao; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Systems Microbiology and Biomanufacturing, 2026)

A neighboring NLR negatively regulates the wheat broad-spectrum resistance protein encoded by Pm21 - Jiaqian Liu; Chaona Si; Shuyun Song; Ziyan Chen; Kaiwen Fan; Ping Hu; Zhenpu Huang; Xiaoxiang Liu; Ruiqi Zhang; Yusheng Zhao; Liping Xing; Aizhong Cao (Science China Life Sciences, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Differentiated grouting reinforcement for mines based on material rheology and coal–rock bonding characteristics - Bowen Fan; Ping Chang; Zhijun Wan; Yuan Zhang; Ruiqiang Liu; Bin Du (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

East Asian monsoon and fluvial processes as joint drivers of detrital material transport along the upper Yellow River during the late Quaternary - Minmin Gao; Yuxin Fan; Fei Wang; Qingsong Cai; Ping Zhang; Chuanying Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Asymmetrical interactions between Ulva prolifera with different health status and its epiphytic diatoms and ciliates - Kai-Ming Sun; Shiliang Fan; Ping Sun; Cuilian Guo; Jing Zhang; Zhenxian Qi; Xiaoxiang Miao; Xiangfeng Kong (Marine Environmental Research, 2026)

Mechanistic investigations into cytochrome c-U(VI) adsorption-reduction on ferrihydrite: Implications for subsurface microbial U redox under anaerobic conditions - Jiayu Song; Huiyang Mei; Xiangxian Ma; Ghufran Uddin; Jianjun Liang; Ping Li; Weichao Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Nanopore characteristics of lower Cambrian shale based on gas adsorption and multifractal analysis: Implications for gas development and CO2 storage - Wei Liu; Xianming Xiao; Ping Gao; Yanming Zhao; Yijie Xing; Qizhang Fan; Guangming Meng; Jinku Li; Qin Zhou; Tengfei Li; Siyi Liu (Fuel, 2026)

Elucidation of calcium coordination mechanisms in cod bone-derived peptides and site-directed mutants using quantum chemistry - Tingting Yang; Qianqian Zhao; Chaozhong Fan; Ping Dong; Hu Hou (Food Chemistry, 2026)

Dual protective function of L-arginine on color and flavor quality of kiwifruit juice during thermal processing - Peipei Guo; Wanying He; Jingzhang Geng; Guangsen Fan; HongLei Tian; Ping Zhan; Peng Wang (Food Chemistry, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Enhancing identification confidence in non-targeted screening of emerging contaminants via an ensemble retention time prediction model: Applications in screening and ecological risk assessment - Ye Liu; Hua-Chun Liu; Tian-Hong Chen; Jian-Ping Deng; Rui-Fang Fan; Hong-Xuan Kuang; Yun-Jiang Yu (Environmental Pollution, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Metabolic flux balancing and enhanced expression of engineered Paeonia lactiflora pinene synthase for high-yield α-pinene production in Serratia marcescens HBQA7 - Ping Zhang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Bioresource Technology, 2026)

Protein Neddylation Beyond Tumor Cells is a Vital Modulator of Anticancer Immunity - Mengna Xu; Weixiao Liu; Fan Liu; Ping Xie (Phenomics, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Spatiotemporal changes in dissolved organic matter chemodiversity and its interaction with microbial composition in heavy-metal polluted river - Chun Liu; Rujie Li; Yuheng Zhang; Lijie Zhang; Zhaoling Liu; Ping Li; Guanghui Fan; Yingjie Zhu; Yue Zuo; Xule Liu; Zhiyong Fu; Xiufeng Zhang (Water Research, 2026)

Mechanical resistance of higher EPS contents in larger granules restricts anammox bacterial growth - Dongdong Xu; Tao Liu; Jiahui Fan; Wenda Chen; Yiyu Li; Meng Zhang; Ping Zheng; Jianhua Guo (Water Research, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Nitrate reduction of dissolved organic carbon exported by episodic upwelling: A novel explanation for negative carbon isotope excursions during the Ediacaran–Cambrian transition - Guangming Meng; Haifeng Gai; Yaowen Wu; Ping Gao; Chengang Lu; Qin Zhou; Tengfei Li; Qizhang Fan; Wei Liu; Yanming Zhao; Yijie Xing; Jinku Li; et al. (Global and Planetary Change, 2026)

Maternal linoleic acid intake disrupts early immune-microbiota-fatty acid programming and increases offspring food allergy risk - Tianliang Bai; Chuang Chen; Huming Shao; Fan Yang; Xing Zhang; Ping Tong; Xuanyi Meng; Yong Wu; Hongbing Chen; Xin Li (Food Bioscience, 2026)

Advanced screening strategies for non-intentionally added substances (NIAS) in plastic food contact materials: Progress and challenges, and future perspectives - Ziying Chen; Yi-Jun Cao; Jie-Ping Fan; Jia Chen (Food Packaging and Shelf Life, 2026)

A new spacetime variational integration approach integrated with ANCF for thin shells and plates with large deformations - Ping Zhou; Hui Ren; Zheng Chen; Wei Fan (Engineering Structures, 2026)

Optimizing watershed ecological management for water conservation by nonlinear effects of meteorological and vegetation drivers - Zikai Ping; Jianmin Bian; Fan Wang; Tao Li (Ecological Engineering, 2026)

Long-term validation and error analysis of MODIS and VIIRS dark target aerosol products in Africa - Xiaoxia Xue; Leiku Yang; Ping Zhang; Muhammad Bilal; Weiqian Ji; Xin Pei; Yizhe Fan; Xiaofeng Lu; Xiaoqian Cheng (Atmospheric Research, 2026)

SIRT3/AARS2 regulates SOD2 lactylation to determine neuronal fate in TBI - Jiazhi Song; Jing Liu; Wenjun Fan; Fang Gou; Hong Yang; Ping Wang; XiaoKun Yang; Kai Tao (Molecular Neurobiology, 2026)

Regulation of Melatonin on AQP4 Expression in Brain of SD Newborn Rats with Bilirubin Encephalopathy and Protection Mechanism - Kaige Xue; Xuefeng Cheng; Weijian Qian; Hemant Mistry; Ping Fan; Jiaheng Hu; Chunyan Chen; Lirong Zhang; Parisa Vazirinasab; Juan Huang; Weitian Lu; Jin Xu; et al. (Molecular Neurobiology, 2026)

Diversity and seasonal dynamics of parasitoid communities sustaining biocontrol of citrus leafminer moth Phyllocnistis citrella - Xin-Yi Chen; Yu-Tong Zhou; Pei-Ping Xu; Ze-Yun Fan; Li-He Zhang; Guillaume Nyagatare; Bao-Li Qiu (Biodiversity and Conservation, 2026)

Convective Mode of Tornadic Storms in Northeastern China: A Preliminary Study - Chao Yuan; Ying Wang; Lei Yang; Fan Ping; Jing Miao; Yingcong Zheng (Advances in Atmospheric Sciences, 2026)

Pollution Status and Remediation Strategies for Potentially Toxic Elements in Baiyin, Northwest China: Lesson from a Typical Resource-Exhausted Mining Area - Ghufran Uddin; Wasim Sajjad; Abdul Haq; Jiayu Song; Ping Li; Qiaohui Fan (Current Pollution Reports, 2025)

Ophiocordyceps polystromata , a new entomopathogenic fungus from the Gaoligong Mountains in western Yunnan, China - He-Fa Liao; Ping-Ping Su; Ze-Mei Chen; Luo-Dong Huang; Qi Fan; Qiu-Lu Yang; Zhu-Liang Yang; Wei-Hong Hu; Yuan-Bing Wang (New Zealand Journal of Botany, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

An explainable ensemble deep learning model for long-term streamflow forecasting under multiple uncertainties - Xinyuan Qian; Bin Wang; Juan Chen; Yukun Fan; Ran Mo; Chengjing Xu; Weifeng Liu; Jing Liu; Ping-an Zhong (Journal of Hydrology, 2025)

Decoding Baijiu flavor complexity: integrating dynamic sensory analysis, high-resolution metabolomics, and advanced mass spectrometry - Bohan Zhang; Yubo Yang; Fanhao Song; Ping Xiang; Fan Yang; Huabin Tu (Food Research International, 2025)

Machine learning-assisted aroma profile prediction in tomato puree based on flavoromics - Zhihui Hu; Yufei He; Sirou Gu; Wanying He; Ping Zhan; Guangsen Fan; Honglei Tian; Hongzhi Wei; Peng Wang (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Abundant and rare microbial subcommunities exhibit different adaptive strategies to temperature stress in Daqu fermentation - Xing Qin; Qingqing Cao; Mengjing Teng; Ying Han; Fan Yang; Ping Xiang; Huabin Tu (Food Bioscience, 2025)

Boosting (E)-nerolidol yield in Serratia marcescens via nerolidol synthase engineering and competitive pathway knockout - Na Chen; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Food Bioscience, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Numerical study on dust distribution in an ultra-large-scale computational domain based on an optimised dust injection condition - Pengju Liu; Ping Chang; Bowen Fan; Lele Wang; Apurna Ghosh; George Barakos (Building and Environment, 2025)

Lactiplantibacillus plantarum ZJ316 Alleviates Helicobacter pylori-Induced Intestinal Inflammation by Sustaining Intestinal Homeostasis - Shiying Wu; Fangtong Wei; Yongqiang Chen; Ziqi Chen; Yuenuo Luo; Jiayi Fan; Yang Xu; Mingyang Hu; Ping Li; Qing Gu (Probiotics and Antimicrobial Proteins, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Predictive value of serum lipid for kawasaki disease shock syndrome: a prospective study - Ping Wu; Bowen Li; Jinlin Wu; Yunhao Li; Fan Ma; Nanjun Zhang; Xiaoliang Liu; Yimin Hua; Kaiyu Zhou; Chuan Wang; Hongyu Duan; Shuran Shao (Immunologic Research, 2025)

Unraveling the functional complexity of the locus coeruleus-norepinephrine system: insights from molecular anatomy to neurodynamic modeling - Chun-Wang Su; Fan Yang; Runchen Lai; Yanhai Li; Hadia Naeem; Nan Yao; Si-Ping Zhang; Haiqing Zhang; Youjun Li; Zi-Gang Huang (Cognitive Neurodynamics, 2025)

LncRNA DBH-antisense RNA 1 modulates the miR-612/SOX4 axis as a CeRNA to regulate the properties of liver cancer stem cells and their resistance to lenvatinib - Guang-zhen Wu; Yang Liu; Yi-wei Ren; Ting-ting Fan; Teng Zhao; Zhi-ping Huang; Kai Lu (Advances in Traditional Medicine, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Sex- and Age-Specific Inverted U-Shaped Links between Dietary Iron Intake and Serum α‑Klotho in Chinese Adults - Baodi Xing; Jie Yu; Yiwen Liu; Qi Gao; Xinyue Chen; Shuli He; Fan Ping; Lingling Xu; Wei Li; Huabing Zhang; Yuxiu Li (Biological Trace Element Research, 2025)

Long-distance, goal-directed movements in western black crested gibbons, Nomascus concolor - Hanchi Zhang; Yu Yang; Ahebota Hazitai; Ping Zhang; Pengfei Fan (Animal Behaviour, 2025)

Identification and characterization of the first G8P[1] sheep rotavirus strain in China: Genetic similarity to human rotavirus and zoonotic potential - DengShuai Zhao; Ping Li; Junyan Fu; YuanHang Zhang; MiaoMiao Zhang; TianYu Wang; DiXi Yu; Han Gao; LiMei Qin; MengMeng Zhao; Feng Wen; ShengFeng Chen; et al. (Veterinary Microbiology, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Remediating the material properties of soil by an innovative micro-nano bubble method - Zhihao CHEN; Zhanyan CHEN; Li WANG; Ping XIANG; Fan YANG; Jiali YU; Jianguo ZHOU; Shunyao ZHUANG; Huabin TU; Yonghong WU (Pedosphere, 2025)

Intensive hierarchical optimal water allocation with uncertainties based on Non-stationary Transformers - Jing Liu; Xin-lei Zhou; Yue-Ping Xu; Zi-Wu Fan (Journal of Hydrology, 2025)

Millennial climate oscillations regulated organic carbon yields from a young orogen during the Last Glacial - Tsun-You Pan; Daidu Fan; Yuan-Ping Chang; James T. Liu (Journal of Asian Earth Sciences, 2025)

Phage therapy modulates the gut microbiome and immune responses in non-typhoidal Salmonella-induced colitis - Md. Sharifull Islam; Ping Wei; Kaimin Zhang; Ishatur Nime; Fan Pan (Food Research International, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

On-site measurements and study on cooling demand characteristics and operational performance of ice storage cooling systems in large-scale sports stadium - Ying Liao; Hecheng Yang; Jiewen Deng; Jiaxing Zhang; Yangyang Su; Wenbo Qiang; Minghui Ma; Chenwei Peng; Jie Bai; Yiwei Ping; Chao Huang; Dexin Fan; et al. (Energy and Buildings, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Microfluidically-engineered enzyme nanoreactors enable biodegradable nanofibrous mats with enhanced antibacterial functionality - Lingling Fan; Yujia Peng; Shaobin Zhang; Bin Xie; Zhengjie Wang; Ziyi Yu; Ping Wei; Weiliang Dong; Min Jiang (Chemical Engineering Journal, 2025)

Engineering a robust and versatile terpenoid production platform in Serratia marcescens HBQA7 - Long Wang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tian Yang; Tai-Ping Fan; Yujie Cai (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair” [Carbohydrate Polymers 314(2023)120899] - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2025)

The microphysical properties and processes in in-flight icing: A case study - Min Yuan; An Lv; Weijia Wang; Xiaobo Dong; Fan Ping (Atmospheric Research, 2025)

Improving aerosol retrieval from FY-3D/MERSI by parameterizing a binary quadratic spectral surface reflectance model with urban percentage and vegetation index - Weiqian Ji; Leiku Yang; Xin Pei; Huan Liu; Yidan Si; Kaimin Sun; Yizhe Fan; Ping Zhang; Xiaoqian Cheng; Xiaofeng Lu (Atmospheric Research, 2025)

Extraction of lithium from cookeite-bearing claystone by chlorination roasting: From thermodynamic calculation to experimental practice - Ya Chen; Penghui Ping; Huoqiang Tang; Renlong Liang; Yongfeng Huang; Xilong Gu; Jiaqing Fan; Jiuqing Liu; Xichang Shi (Minerals Engineering, 2025)

Enhanced photoelectrochemical degradation of trichloroethylene using internal Z-scheme g-C3N4/TNAs: Performance evaluation and proposed mechanism - Wu-Xing Chen; Yen-Ping Peng; Chia-Hung Chen; Amila Kasun Abeysinghe; Po-Yen Chien; Ku-Fan Chen; Fang Yu Liang (Journal of Environmental Chemical Engineering, 2025)

Adverse pulmonary effects and metallic characteristic of size-resolved welding fumes in human lung epithelial BEAS-2B cells - Pin-Hao Qiu; Chia-Hua Lin; Yen-Ping Peng; Ku-Fan Chen; Yi-Chun Chen; Yung-Chang Lin; Chia-Hsiang Lai (Environmental Toxicology and Pharmacology, 2025)

Multi-strategy metabolic reprogramming of Serratia marcescens HBQA7 for high-efficiency spermidine biosynthesis via the carboxyaminopropylagmatine pathway - Linbo Gou; Jie Wang; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Yujie Cai (Chemical Engineering Journal, 2025)

Pre-coordination synthesis of active Fe single-atom catalyst enabling efficient and ultralong-life oxygen depolarized cathode applications - Ping Li; Chengbin Wang; Guitao Zhang; Kaicai Fan; Yifei Liu; Bin Li; Porun Liu; Lingbo Zong; Lei Wang (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Multi-mineral dating of Archean granitoids of the Jiaobei Terrane: Decoding multiple tectono-thermal events in the eastern North China Craton - Yan-Ping Chen; Fan-Mei Kong; Xu-Ping Li; Hans-Peter Schertl (Precambrian Research, 2025)

Reductive transformation processes of ferrihydrite and U(VI) triggered by S2- under an anaerobic environment - Jiayu Song; Shirong Qiang; Huiyang Mei; Ping Li; Jianjun Liang; Qiaohui Fan (Journal of Hazardous Materials, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Hydrogen-rich syngas production from the steam co-gasification of low-density polyethylene and coal refuse - Sittichai Natesakhawat; Jennifer Weidman; Nicholas C. Means; Bret H. Howard; Fan Shi; Jonathan Lekse; McMahan Gray; Ping Wang (Fuel, 2025)

Rational screening of covalent organic frameworks for solid-phase microextraction of advanced glycation end products from thermally processed foods - Xiao-Fan Lu; Xin-Yu Li; Rongyu Wang; Wenhua Ji; Jian-Ping Ma; Dian-Shun Guo (Food Chemistry, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Recent progress on fluorescence labeling of bacteria: Binding strategies, probes, and applications - Ping Yu; Yang Liu; Qingwei Song; Sihua Qian; Junjie Fan; Ying Liu; Yunwei Wei; Kaizhe Wang; Yuhui Wang (Chemical Engineering Journal, 2025)

Macrophage-targeted lipid nanoparticles based on Dendron-like lipids deliver mTOR inhibitor to alleviate systemic lupus erythematosus - Keqian Du; Guantao He; Fujian Huang; Xi Zhang; Xiaohan Zhang; Junjin Jie; Chan Huang; Yuqiong Wu; Huiyang Fan; Zhiming Lin; Lin-Ping Wu (Chemical Engineering Journal, 2025)

Alkaloids from Zanthoxylum nitidum and their anti-proliferative activity against A549 cells by regulating the EGFR/AKT/mTOR pathway - Fan-Fan Wang; Ping-Fang Tao; Yu-Jun Zhong; Yun-Qiong Gu; Cai Yi Wang; Feng Qin (Natural Product Research, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Prenatal arsenic exposure disrupts placental angiogenesis by altering Pdgfb promoter epigenetic modification - Yu Zhang; Ya-Ping Song; Hong-Yan Wu; Fang-Jie Zhong; Hao Xue; Yi-Jun Fan; Cheng Zhang; De-Xiang Xu (Journal of Hazardous Materials, 2025)

Self-reinforcing extraction of uranium(VI) from wastewater via uranium-incorporated hematite photoelectrochemical system - Jiacheng Wu; Jingjing Wang; Yueran Qi; Zena Zhang; Yue Li; Fan Chen; Ping Li; Yuheng Wang (Journal of Hazardous Materials, 2025)

Highly sensitive detection of triethylamine by EuFeO3-based gas sensor - Yinyue Wang; Shuyi Ma; Ping Ni; Nina Ma; Gege Fan; Jiayun Guo; Jiamin Zhu; Heng Wang (Journal of Environmental Chemical Engineering, 2025)

Identifying the determinants of natural, anthropogenic factors and precursors on PM1 pollution in urban agglomerations in China: Insights from optimal parameter-based geographic detector and robust geographic weighted regression models - Ping Zhang; Yong Wang; Wenjie Ma; Mingyao Li; Yonghua Zhao; Wentao Wang; Yefan Jia; Jinghao Fan; Lufang Kong; Kang Hou; Yuanyuan Han (Environmental Research, 2025)

Distribution characteristics and risk assessment of hexabromocyclododecanes in soil from e-waste dismantling areas - Jun Pan; Ping Ding; Jiaji Zhang; Chushan Huang; Lijuan Zhang; Wei Huang; Yuqing Fan; Guocheng Hu (Environmental Geochemistry and Health, 2025)

The efficacy of Perilla frutescens rotation and Trichoderma harzianum application in mitigating continuous cropping challenges of Panax notoginseng - Yan WANG; Yingpin LIU; Guobing TIAN; Shengchao YANG; Junwen CHEN; Shuhui ZI; Wei FAN; Qiaoran MA; Jiamin LIU; Ping ZHAO; Shuran HE (Applied Soil Ecology, 2025)

Intercropping enhances stable soil organic carbon pool through macroaggregate protection and biochemical recalcitrance interactions - Ding Wang; Wenchun Yu; Chunyan Ming; Linkang Chen; Ping Zhao; Xiaojun Shi; Zhengxiong Zhao; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2025)

Underrated risk of antibiotic resistance genes dissemination mediated by bioaerosols released from anaerobic biological wastewater treatment system - Na-Na Han; Xue-Ping Wang; Jing-Ao Jin; Wen-Hui Li; Wen-Ya Yang; Nian-Si Fan; Ren-Cun Jin (Water Research, 2025)

Multiscale spatio‐temporal variability of suspended sediment front in the Yangtze River Estuary and its ecological effects - Yunfei Du; Xiangju Han; Ya Ping Wang; Daidu Fan; Jicai Zhang (Water Research, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Effects of exogenous mineral silicon on physiological characteristics and arsenic uptake and transport in rice - Jing Han; Qihao He; Mingjing Lei; Ke Li; Yufei Zhou; Wenmin Li; Ying Xiao; Fan Zhang; Chang Sun; Jieying Wang; Jian Zhu; Zhiming Liu; et al. (Journal of Hazardous Materials, 2025)

Biomineralization mechanisms in the estuarine oyster (Crassostrea ariakensis): Unveiling the adaptive potential of mollusks in response to rapid climate change - Shen-Tong Wang; Li Li; Qi Yang; Wei Wang; Lu-Ping Wang; Shou-Du Zhang; Guo-Fan Zhang (Environmental Pollution, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Study on the high-efficiency CO2 mineralization reaction mechanism of thermally modified materials from neutralized gypsum residue driven by sulfur vacancies in an aqueous environment - Yuwen Deng; Sisi Chen; Huidong Tang; Fei Wang; Yixing Ma; Lei Shi; Fan Du; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Engineering of farnesyl pyrophosphate hydrolase for farnesol production in Serratia marcescens - Xia Chen; Di Liu; Long Wang; Yao Lu; Yongai Ma; Tai-Ping Fan; Yujie Cai (Systems Microbiology and Biomanufacturing, 2025)

A Unified Nonlinear Creep Damage Coupled Model for Rocks Based on Fractional Calculus and Statistical Damage Model - Da-Lang Tian; Zheng-Chuan Li; Fan Shen; Yu-tong Li; Zheng Li; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Lithofacies Types and Pore Structure Characteristics of Marine Shale in the Lower Cambrian Shuijingtuo Formation, Middle Yangtze Region, China - Jialin Fan; Wei Liu; Yujing Qian; Jinku Li; Qin Zhou; Ping Gao (Journal of Marine Science and Engineering, 2025)
The lithofacies and pore structural characteristics of shale reservoirs directly affect the exploration and development of shale gas. To clarify the exploration and development potential of the Lower Cambrian Shuijingtuo Formation (SJT) shale in the Middle Yangtze region, China, this study employs integrated experimental approaches, including optical and scanning electron microscopy (SEM) observations, X-ray diffraction (XRD) mineralogical analysis, and low-pressure gas (N2/CO2) adsorption, to classify mudstone lithofacies within the SJT and elucidate pore structural characteristics and dominant geological control across different lithofacies. The research results show that (1) Six main types of shale lithofacies are found in the STJ, including low-TOC massive calcareous mudstone (LMCM), low-TOC laminated mixed mudstone (LLMM), medium-TOC massive mixed mudstone (MMMM), high-TOC massive mixed mudstone (HMMM), high-TOC laminated siliceous mudstone (HLSM), and laminated argillaceous mudstone (LAM). (2) The pore types of SJT mudstone primarily include organic pores, intragranular clay mineral pores, and microfractures. The pore structure of mudstone is mainly controlled by clay mineral content and TOC content. However, the controlling factors of pore structure vary among different mudstone lithofacies. LMCM and LLMM are dominated by intragranular clay mineral pores, with their pore structures mainly controlled by clay mineral content. The pore types of HLMM and HLSM are organic pores, with pore structures predominantly controlled by TOC content. (3) The SJT mudstone gas reservoir exhibits diverse types, including HLSM, LAM, and LLMM. HLSM is characterized by the highest brittleness index and elevated pore volume (PV) and it can be considered the optimum lithofacies in the study area. Additionally, LLMM has the highest PV and relatively high brittleness index, positioning it as another significant reservoir target in the study area. Therefore, the Lower Cambrian shale gas reservoirs in the Middle Yangtze region exhibit diverse reservoir types. These research findings provide a scientific basis for the next phase of shale gas exploration planning in the Lower Cambrian.

Effects of pterostilbene on inducing apoptosis in normal bladder and bladder cancer cells - Chen-Hsun Ho; Chia-Kwung Fan; Yi-Chen Chu; Shih-Ping Liu; Po-Ching Cheng (Tissue and Cell, 2025)

Computationally-assisted wearable system for continuous cortisol monitoring - Ying Liu; Xiaoyu Su; Peidi Fan; Xin Liu; Yuxiang Pan; Jianfeng Ping (Science Bulletin, 2025)

A stochastic decision-making framework for optimal multi-objective reservoir operation accounting for the tracking of uncertainty propagation and evolution from multiple sources - Feilin Zhu; Yurou Zeng; Yaqin Wang; Weifeng Liu; Mingyu Han; Yukun Fan; Mengxue Ben; Ping-an Zhong (Journal of Hydrology, 2025)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Binding mechanism and safety assessment of BADGE from epoxy-coated cans and protein - Yu-Jie Shi; Fan- Gong; Chang-Ying Hu; Zhi-Wei Wang; Jun-Peng Hu; Yan-Ping Xian (Food Chemistry, 2025)

Formation of aroma characteristics driven by microorganisms during long-term storage of Liubao tea - Chang Xu; Jinming Zhang; Yani Pan; Xinyu Feng; Anran Yan; Xinxin Wang; Lin Xiang; Haowei Guo; Lixin He; Tianyuan Chen; Fangyuan Fan; Shuying Gong; et al. (Food Chemistry, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Digital twin-based winter wheat growth simulation and optimization - Xin Xu; Feng Gao; Du Xiong; Zehua Fan; Shuping Xiong; Ping Dong; Hongbo Qiao; Xinming Ma (Field Crops Research, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Numerical Analysis of Nonorthogonal Shear Failure in Rock Joints Under CNL Conditions - Bohua Hu; Peng Yin; Wenchen Fan; Ping Cao (Geotechnical and Geological Engineering, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Ruthenium-doped molybdenum boride for electrocatalytic hydrogen evolution - Xiang Wang; Panfeng Fan; Yu Xie; Long Zhang; Jiawei Jiang; Ping Huang; Muhammad Ahmad; Yaru Cheng; Jie Zhao (Fuel, 2025)

Flexural fatigue behavior of FRP-reinforced UHPC tubular beams - Tian-Hui Fan; Jun-Jie Zeng; Xianwen Hu; Jun-Da Chen; Ping-Ping Wu; Hui-Tao Liu; Yan Zhuge (Engineering Structures, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Variation characteristics and impact factors of the co-occurrence of surface ozone and particulate matter over the Southern Sichuan region, China - Ping Shao; Siyuan Wang; Chaoyong Tu; Shumin Chen; Xianyu Yang; Shenglan Zeng; Jin Fan; Shaobo Zhang; Changjian Ni; Shigong Wang (Natural Hazards, 2025)

Optimized irrigation level and deep vertical rotary tillage depth enhanced seed cotton yield, water-nitrogen productivity and economic benefit by reducing soil salinity: evidence from southern Xinjiang of China - Zhentao Bai; Ling Li; Zhijie Li; Pengfei Li; Tangang Wang; Junliang Fan; Ping Gong; Hongguang Liu (Irrigation Science, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Four new pregnane C21 steroids isolated from the roots of Cynanchum auriculatum - Yi-min Fan; Ping Yi; Jun Jin; Jun-you Jian; Wei Gu; Chun-mao Yuan; Zhan-xing Hu; Xiao-jiang Hao; Lie-jun Huang (Natural Product Research, 2025)

Pepper feeding derivative Brucella sp. in the gut of Spodoptera litura (Lepidoptera: Noctuidae) affect the growth and development of host larvae - Yu Wang; Zhou Yu; Bei-Long Chen; Shao-Shao He; Zi-Yao Liu; Zheng Zhai; Lin Chen; Jiang-Bin Fan; Huan Yu; Zhi-Ping Zuo; Yong-Sheng Zhang (Pesticide Biochemistry and Physiology, 2025)

Carbon dots bridging interface engineering of PVDF-HFP/ZnO nanoarrays cross-linked porous membranes for wastewater purification - Ping Huang; Mingda Wang; Shunjian Xu; Lei Liu; Haiyan Fu; Wei Zhong; Jirui Fan; Wenxiang Xue; Zonghu Xiao; Jianhua Huang (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Data-driven pipeline modeling for predicting unknown protein adulteration in dairy products - Huihui Yang; Yutang Wang; Jinyong Zhao; Ping Li; Zhixiang Li; Long Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2025)

Characterization of flavor profiles and microbial communities in Ciba chili fermentation using metagenomics, untargeted metabolomics, and flavoromics - Tianyang Wang; Yiling Xiong; Haibin Yuan; Xiangbo Xu; Xiangling You; Chunyuan Ping; Wenjiao Fan; Wei Chen; Hongfeng Jia; Huachang Wu; Ju Guan (Food Bioscience, 2025)

Robust lubricity and multifunctional water-based lubrication system induced by ionic liquids with its interfacial self-assembly behavior and unique hydration structure - Mengyao Liu; Yingying Yao; Bingyu Tian; Kun Cui; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2025)

Impressive merits of Nanocellulose driving sustainable beauty - Xiangyu Wang; Chunyan Zhong; Yuguang Zhong; Zhixiong Fan; Zhiren Liu; Ping Xu; Xinxin Deng; Jiaqi Guo; Trupti Rohan Sawant; Mengbo Zhou; Qianqian Wang; Huan Liu; et al. (Carbohydrate Polymers, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Potential Predictive Value of Platelet Distribution Width for Functional Outcome After Ischemic Stroke - Tong Shen; Junfen Fan; Yangmin Zheng; Yumin Luo; Ping Liu (Molecular Neurobiology, 2025)

Network pharmacology analysis and molecular mechanism of paeoniflorin and its metabolite in prolactinoma cells - Min Cao; Lun-shan Xu; Ping Huang; Bin-bin Fan; Yi-hua Zhang (Molecular Diversity, 2025)

The synergistic effect of Rhizophagus irregularis and Biochar on the growth of Switchgrass under sodium-saline-alkali stress: insights from soil mechanical property analysis - Yuqiang Wen; Tianle Xu; Wei Chang; Kun Li; Xiaoxu Fan; Yuan Ping; Fuqiang Song (Mycorrhiza, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Interactions between riverine sediment organic matter molecular structure and microbial community as regulated by heavy metals - Ping Li; Chun Liu; Lijie Zhang; Zhaoling Liu; Zhiyong Fu; Guanghui Fan; Yingjie Zhu; Yue Zuo; Liqiong Li; Lisha Zhang (Journal of Hazardous Materials, 2025)

Improving bioavailability of lignocellulosic biomass by pretreatment with the marine fungus Chaetomium sp. CS1 - Minghuang Ling; Ping Zheng; Xiaomei Huang; Gaili Fan; Huafeng Zhang; Zhijie Xu; Peiwen Zhuang; Changyou Wang; Hans-Peter Grossart; Kai Zhang; Zhuhua Luo (International Biodeterioration & Biodegradation, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Pricing eco-products using happiness data: The case of China - Bangzhu Zhu; Xiaozhen Fan; Ping Wang (Environmental Impact Assessment Review, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Landslide displacement prediction using time series InSAR with combined LSTM and TCN: application to the Xiao Andong landslide, Yunnan Province, China - Jia Li; Chengpeng Fan; Kang Zhao; Zhike Zhang; Ping Duan (Natural Hazards, 2025)
Research on landslide displacement prediction based on interferometric synthetic aperture radar (InSAR) deformation data involves two main issues. First, InSAR can provide only one-dimensional deformation data along the satellite’s line of sight (LOS), which cannot truly reflect the deformation of the landslide body in the downward direction along the slope. Second, the use of a single prediction model does not adequately account for both long-term and local changes in landslide displacement, affecting the accuracy of the predictions. To address this, in this study, Long Short-Term Memory networks (LSTM) and temporal convolutional network (TCN) models are combined to construct a method (LSTM-TCN) of landslide displacement prediction. This method can consider the long-term and localized changes in landslide displacement. The method is first based on InSAR technology to obtain surface deformation. The deformation of the landslide is subsequently computed in the downward direction along the slope to obtain the landslide displacement time series data. Next, the LSTM-TCN is used for landslide displacement prediction. Finally, the mean absolute error (MAE), root mean square error (RMSE) and coefficient of determination (R 2 ) are used to evaluate the performance of the model. The experiment is conducted on the Xiao Andong landslide in Anshi village, Fengqing County, Lincang City, Yunnan Province, China. The LSTM-TCN model achieves an R 2 of 0.75, an RMSE of 0.43 cm, and an MAE of 0.36 cm. Compared with the individual LSTM and TCN models, the LSTM-TCN model exhibits the highest prediction accuracy and the smallest prediction error, which is closer to the true result that in the other models. These results demonstrate that the combined LSTM-TCN model effectively captures the complex features and long-term trends in landslide displacement data, significantly enhancing the accuracy of predictions.

Risk assessment of rip current in China: based on data from 33 beaches - Wenwen Tang; Qi Chen; Yibing Zong; Fan Zhang; Ya Ping Wang; Jianjun Jia (Geo-Marine Letters, 2025)

Catalytic oxidation of toluene over the low-grade palygorskite clay from Linze region supported highly dispersed Mn Ce oxides catalysts: Preparation and performance - Xuehua Zou; Xinyu Guo; Mengyuan Peng; Lanlan Dai; Fan Xu; Ping Zhang; Yuefei Zhou; Tianhu Chen; Chengzhu Zhu; Qiaoqin Xie (Applied Clay Science, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Establishment and application of a sandwich ELISA method for measuring Toxoplasma gondii circulating fructose-1,6-bisphosphate aldolase (ALD) protein in cats - Jing-Zhi Gong; Yi-Min Fan; Yun-Ping Wu; Ming Pan; Zhao-Feng Hou; Si-Yang Huang (Veterinary Parasitology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Microplastics in fish species from the eastern Guangdong: Implications to Indo-Pacific humpback dolphin (Sousa chinensis) and human health - Jinyan Liu; Qilin Gutang; Yingping Fan; Ran Bi; Puhui Zhao; Keqin Zhang; Zewei Sun; Ping Li; Wenhua Liu; Jianxin Wang (Marine Environmental Research, 2025)

Revisiting the high temperature Darongshan-Shiwandashan granitoids in the South China: A response to slab tearing associated with diachronous collision between Indochina and South China blocks - Yu-Fan Yue; Xiao-Ping Xia; Pengfei Li; Bin He; Touping Peng; Min Sun; Jian Xu; M.P. Manu Prasanth (Lithos, 2025)

Cerium-based nanohydrolase for fast catalytic hydrolysis of β-lactam antibiotics in wastewater effluents - Wen-Yuan Fan; Xin Zhang; Dong-Hua Xie; Kenneth Mei Yee Leung; Guo-Ping Sheng (Journal of Hazardous Materials, 2025)

Metagenomic insight into the diffusion signal factor mediated social traits of anammox consortia after starvation - Xue-Ping Wang; Na-Na Han; Jia-Hui Yang; Nian-Si Fan; Ren-Cun Jin (Journal of Environmental Management, 2025)

Liubao tea extract restrains obesity-related hyperlipidemia via regulation of AMPK/p38/NF-κB pathway and intestinal microbiota - Xinyu Feng; Yuechao Qin; Shicheng Ma; Shengjin Ming; Zhihang Weng; Yuqi Xuan; Shuying Gong; Fangyuan Fan; Ping Chen; Qiang Chu; Zhongxia Li (Food Chemistry, 2025)

Flowering in aged white tea: Recovering umami taste and amplifying of stale aroma - Wan Zhu; Xinyu Feng; Yani Pan; Haowei Guo; Yunqing Liu; Xingchen Lin; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Molecular characteristics of three complete genome sequences of apple rubbery wood virus 1 isolates from apple trees in China - Cheng-long Liu; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Guo-Jun Hu; Ya-Feng Dong (Journal of Plant Pathology, 2025)

Sequestration process and mechanism of U(VI) on montmorillonite-aspergillus niger composite - Rongyue Geng; Shirong Qiang; Huiyang Mei; Beihang Zhang; Ping Li; Jianjun Liang; Qiaohui Fan (Science of The Total Environment, 2025)

Aliphatic amine-modified recombinant endoskeleton UiO-66 efficiently enhances CO2 capture performance - You-yun Gong; Zi-ang Jia; Yiwen Fan; Jin-ping Cheng (Process Safety and Environmental Protection, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Novel method for predicting concentrations of incineration flue gas based on waste composition and machine learning - Ya-Ping Qi; Pin-Jing He; Dong-Ying Lan; Fan Lü; Hua Zhang (Journal of Environmental Management, 2025)

Gradient-temperature control enhances oxi-upcycling of polyethylene plastics to dicarboxylic acids over TS-1 zeolite - XueYang Hou; Fan Yuan; Xiaodong Liu; Kaili Wang; Yi Zhu; Ping Cheng; Rongrong Jia; Liyi Shi; Lei Huang (Chemical Engineering Journal, 2025)

Biomimetic superparamagnetic gelatin/chitosan asymmetric fibrous membrane for accelerating wound healing under static magnetic field - Jingxi Wang; Kun Li; Yunxue Jia; Tianran Song; Junwei Xu; Xuemei Sun; Meili Liu; Ping Li; Yubo Fan (Carbohydrate Polymers, 2025)

Sevoflurane postconditioning mitigates neuronal hypoxic-ischemic injury via regulating reactive astrocytic STAT3 protein modification - Yufei Jia; Yanhong Song; Hang Xue; Xingyue Li; Yinong Zhang; Shiyue Fan; Xu Yang; Zixuan Ding; Yue Qiu; Ziyi Wu; Ping Zhao (Chemico-Biological Interactions, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Targeting Brain Endothelial Gasdermin D: A Shortcut to Remodel the Blood-Brain Barrier - Zhou-Yue Wu; Yi-Fan Luo; Ya-Ping Lu; Yi-Xuan Zhang; Feng Han (Neuroscience Bulletin, 2025)

Interaction between resveratrol and SIRT1: role in neurodegenerative diseases - Lin Zhu; Miaomiao Yang; Lehao Fan; Qiuying Yan; Lifeng Zhang; Ping Mu; Fangjin Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Two distinct evolutions of extreme precipitation over central eastern China during June and July - Renguang Wu; Peijun Zhu; Panxi Dai; Fan Ping; Jianjiang Wang; Chengyan Mao; Yanan Liu (Climate Dynamics, 2025)

Di-(2-ethylhexyl) Phthalate Exposure Induces Developmental Toxicity in the Mouse Fetal Heart via Mitochondrial Dysfunction - Yafei Guo; Bowen Li; Yu Yan; Nanjun Zhang; Shuran Shao; Lixia Yang; Lixue Ouyang; Ping Wu; Fan Ma; Hongyu Duan; Kaiyu Zhou; Yimin Hua; et al. (Cardiovascular Toxicology, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Unveiling the non-linear effects of water and oil on hyperspectral imaging-based characterization of solid waste by hyperspectral unmixing - Dong-Ying Lan; Pin-Jing He; Ya-Ping Qi; Fan Lü; Hua Zhang (Waste Management, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Variations of water and sediment flux from the Yellow River estuary over decades and estuarine dynamic erosion and accumulation shifts - Peiyu Zhang; Ping Li; Jun Du; Yaoshen Fan; WenWen Yan (Regional Studies in Marine Science, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Single nucleus RNA sequencing reveals cellular and molecular responses to vanadium exposure in duck kidneys - Na Qiao; Xueyan Dai; Jing Chen; Huabin Cao; Guoliang Hu; Xiaoquan Guo; Ping Liu; Chenghong Xing; Fan Yang (Journal of Hazardous Materials, 2024)

Cooperative application of transcriptomics and ceRNA hypothesis: lncRNA-00742/miR-116 targets CD74 to mediate vanadium-induced mitochondrial apoptosis in duck liver - Jing Chen; Xueyan Dai; Chenghong Xing; Yike Zhang; Huabin Cao; Guoliang Hu; Xiaoquan Guo; Xiaona Gao; Ping Liu; Fan Yang (Journal of Hazardous Materials, 2024)

Effects of compound emulsifiers on the characteristics and stability of nano-emulsions from pollock bones - Chaoxin Tu; Honglin Zhu; Tingting Yang; Jiangjiang Zhang; Xue Zhao; Ping Dong; Yan Fan; Hu Hou (Food Chemistry, 2024)

Anti-inflammatory diet mitigate cardiovascular risks due to particulate matter exposure in women during pregnancy: A perspective cohort study from China - Ping Zu; Lei Zhang; Kun Zhang; Liping He; Yujie Fan; Chenxi Zhou; Yunlong Chen; Ying Zhang; Ruixue Tao; Xianxia Chen; Peng Zhu (Environmental Research, 2024)

Biomimetic Stylophora pistillata-like NiMoO4/NiFeS crystalline–amorphous phase boundary activated lattice oxygen mechanism for efficient electrochemical water oxidation - Weikai Fan; Chaofan Liu; Jiang Wu; Hao Zhou; Tao Jia; Yang Ling; Ping He; Qunzhi Zhu; Zaiguo Fu; Mingze Ou; Jia lin; Zhongwei Chen (Chemical Engineering Journal, 2024)

Impact of photochemistry on wintertime haze in the Southern Sichuan Basin, China - Siyuan Wang; Ping Shao; Xianyu Yang; Jianjun Wu; Shaolei Zhang; Shenglan Zeng; Jin Fan; Changjian Ni; Shigong Wang (Atmospheric Pollution Research, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Neuroprotection by tetramethylpyrazine and its synthesized analogues for central nervous system diseases: a review - Fan Feng; Ding-Qiao Xu; Shi-Jun Yue; Yan-Yan Chen; Yu-Ping Tang (Molecular Biology Reports, 2024)

Association of Oxidative Stress on Cognitive Function: A Bidirectional Mendelian Randomisation Study - Zhixing Fan; Chaojun Yang; Xiaoling Qu; Jing Zhang; Hui Wu; Ying Yang; Yifan Huang; Ping Zeng; Zujin Xiang; Jian Yang (Molecular Neurobiology, 2024)

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Abnormal Changes of IL3/IL3R and Its Downstream Signaling Pathways in the Prion-Infected Cell Line and in the Brains of Scrapie-Infected Rodents - Xiao-Xi Jia; Cao Chen; Chao Hu; Zhi-Yue Chao; Wei-Wei Zhang; Yue-Zhang Wu; Qin Fan; Ru-Han A; Xin Liu; Kang Xiao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2024)

Symbiotrophs dominate rhizosphere soil fungal community stability of the Cathaya argyrophylla - Zhibo Zhou; Peng Xie; Kerui Huang; Ping Mo; Aihua Deng; Shaogang Fan; Binbin Long; Yun Wang (Applied Soil Ecology, 2024)

Fracture prediction method for deep coalbed methane reservoirs based on seismic texture attributes - Bing Zhang; Xue-mei Qi; Ya-ping Huang; Hai-feng Zhang; Fan-rui Huang (Applied Geophysics, 2024)

Advancement and challenges in tea brewing: The dynamic principles, influencing factors, innovative processing technologies and pollutants - Yunqing Liu; Xinyu Feng; Ting Gao; Yani Pan; Helin Lv; Ming Chen; Yili Shen; Wan Zhu; Yuye Yao; Lixin He; Shuying Gong; Fangyuan Fan; et al. (Trends in Food Science & Technology, 2024)

Comprehensive investigation on the reinforcement effect of the dynamic compaction of high stone-filled embankments - Ping Xu; Wei Zhao; Shi-fan Qiao; Hui Dong (Transportation Geotechnics, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Physical and mechanical characterization of solid waste collected from rural areas of China: Experimental study - Yu-Ping Li; Baoyun Fan; Le Cheng; Jianyong Shi; Xiulei Li; Lianghu Su; Zeeshan Khursheed (Process Safety and Environmental Protection, 2024)

Rheological properties of the swim bladder colloid from Atlantic cod (Gadus Morhua) and its digestive characteristics - Qian Zhang; Xuening Zhang; Yan Fan; Hongwei Zhang; Ming Kong; Ping Dong; Xue Zhao; Hu Hou (Food Hydrocolloids, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Recent research progress on recycling metallurgical waste slag and strengthening directional recovery of impurity elements by applied electric field - Wen-zhi Xia; Yun Zhou; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren; Zhi-you Liao; Hai-chuan Wang (Chemical Engineering Journal, 2024)

Role of diffusible signal factor in regulating aerobic granular sludge formation under temperature shocks - Aiqi Tang; Shengqiang Fan; Ping Zhang; Ang Li (Bioresource Technology, 2024)

Using the space-time evolution spectrum to investigate the transmission characteristics of lightning return stroke current - Fan Zhang; Hong Deng; Ping Yuan; Tingting An; Lizhen Yuan; Liwen Xu (Atmospheric Research, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Light attenuation parameterization in a highly turbid mega estuary and its impact on the coastal planktonic ecosystem - Qiyinan Lin; Zhixuan Feng; Yihe Wang; Xue Wang; Zhaoxuan Bian; Fan Zhang; Fang Cao; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2024)
Light is essential for phytoplankton photosynthesis and many other biogeochemical processes in the aquatic system. However, light regimes vary greatly in the estuaries and coasts due to the optical complexity of the Case-2 waters. In this study, observed vertical profiles of photosynthetically active radiation (PAR; 400-700 nm) in a highly turbid mega estuary, the Changjiang (Yangtze River) Estuary, are used to quantify the effects of sedimentary and biogeochemical components on PAR attenuation in the water column and associated ecological impacts. The in-situ data suggest suspended sediment plays the most crucial role in light diffuse attenuation coefficient (K d ) distribution, followed by salinity (i.e., an index for colored dissolved organic matter) and phytoplankton chlorophyll-a. A new parameterization of K d , based on suspended sediment, chlorophyll-a concentration, and salinity, is fitted using multiple linear regression. The previous and new K d parameterizations are further applied to a coupled hydrodynamics-sediment-ecosystem model to simulate spring phytoplankton blooms. Comparative model runs reveal that the new K d parameterization resulted in a better representation of the spring bloom patterns in magnitude, horizontal distribution, and vertical thickness of the high chlorophyll-a band offshore the turbidity maximum zone during the spring bloom. In summary, accurate representations of underwater light fields in the optically complex Case-2 water are critical in understanding biophysical processes that control planktonic ecosystem dynamics in the estuaries and coastal seas.

Quorum sensing mediated response mechanism of anammox consortia to anionic surfactant: Molecular simulation and molecular evidence - Xue-Ping Wang; Na-Na Han; Zi-Yan Xu; Yu-Hui Zhu; Gui-Feng Li; Nian-Si Fan; Ren-Cun Jin (Science of The Total Environment, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Biofilm-induced heterogeneity toward anammox bacteria distribution and metabolome - Na-Na Han; Xue-Ping Wang; Jia-hui Yang; Nian-Si Fan; Ren-Cun Jin (Chemical Engineering Journal, 2024)

Applewood Biochar at Different Smoldering Conditions Passivates Pyrite by Promoting the Formation of Jarosite - Hecheng Fu; Jiale Fan; Jie Li; Jianhong Huang; Senlin Tian; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2024)

Assessment on eco-environmental quality of the Yellow River Basin by considering desertification index - Min An; Fan Meng; Weijun He; Fang Xue; Mengfei Song; Ping Xie; Bei Wang (Journal of Mountain Science, 2024)

Environmental microbes alleviate antibiotic disturbance on plant endophytes in aquatic microcosms: Prospects for conferring fitness benefits - Yi Hu; Fan-Li Meng; Jia-Heng Zhao; Guo-Ping Sheng (Water Research, 2024)

Simulating liquefaction-induced resuspension flux in a sediment transport model - Zichen Zhu; Xing Du; Bingchen Liang; Linfeng Wang; Yupeng Song; Ping Li; Yaoshen Fan; Shuhua Bian; Yongzhi Wang; Yongqiang Zhang; Bing Li (Water Research, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

Preparation, typical structural characteristics and relieving effects on osteoarthritis of squid cartilage type II collagen peptides - Qianqian Zhao; Zhaoxia Li; Zeyu Liu; Xue Zhao; Yan Fan; Ping Dong; Hu Hou (Food Research International, 2024)

Golden-flower fungus (Eurotiwm Cristatum) presents fungal flower aroma as well as accelerates the aging of white tea (Shoumei) - Wan Zhu; Su Zhou; Haowei Guo; Jiali Hu; Yanyan Cao; Yingxin Xu; Xingchen Lin; Baoming Tian; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2024)

A simple and universal approach for fabricating bioactive self-stacked hydrogels with enhanced therapeutic efficacy - Wenxin Zhang; Shubi Zhao; Hui Zhang; Xinpeng Wang; Jingxi Wang; Tianran Song; Ping Li; Yubo Fan (Chemical Engineering Journal, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Platelet membrane coated Cu9S8-SNAP for NIR-II photoacoustic imaging guided NO repairing acute kidney injury - Xiaojuan Hu; Danping Wu; Shijie Yao; Gongning Chen; Ping Li; Yang Chen; Wancheng Gong; Weijiao Fan; Xiaoyi Chen; Xiaozhou Mou; Yu Cai; Xianghong Yang (Chemical Engineering Journal, 2024)

Freeze-thaw effects on pore structure of clay by 3D X-ray computed tomography and mercury intrusion porosimetry - Wenhu Fan; Ping Yang; Shengfu Wang; Zhaohui (Joey) Yang; Xiaofeng Fan; Yong Tao (Cold Regions Science and Technology, 2024)

Yellow tea: more than turning green leaves to yellow - Xinyu Feng; Shiyan Yang; Yani Pan; Su Zhou; Shicheng Ma; Cansong Ou; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Critical Reviews in Food Science and Nutrition, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Enhancing visible-light-driven photocatalysis: unveiling the remarkable potential of H2O2-assisted MOF/COF hybrid material for organic pollutant degradation - Amila Kasun Abeysinghe; Yen-Ping Peng; Po-Jung Huang; Ku-Fan Chen; Chia-Hung Chen; Wu-Xing Chen; Fang-Yu Liang; Po-Yen Chien (Environmental Science and Pollution Research, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

Dynamic changes in the non-volatile and flavour compounds in withered tea leaves of three different colour cultivars based on multi-omics - Yulong Ye; Yiyun Gong; Ping Huang; Fan Luo; Renyou Gan; Chunyan Fang (Food Chemistry, 2024)

Screening and verification of outer membrane proteins of Cronobacter sakazakii with potential adhesion capability to human ileocecal adenocarcinoma cells - Chumin Zhao; Ping Li; Yufei Fan; Dongdong Zhu; Jingbo Jiao; Yue Li; Zehui Xiao; Xinjun Du; Shuo Wang (Food Bioscience, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Exploitation of multiple host-derived nutrients by the yellow catfish epidermal environment facilitates Vibrio mimicus to sustain infection potency and susceptibility - Yang Feng; Jiao Wang; Wei Fan; Bowen Huang; Zhenyang Qin; Ziqi Tian; Yi Geng; Xiaoli Huang; Ping Ouyang; Defang Chen; Weimin Lai (Fish & Shellfish Immunology, 2024)

Genome-wide identification, characterization, molecular evolution and expression profiling analysis of scavenger receptors in black rockfish (Sebastes schlegelii) - Zhentao Chen; Xuangang Wang; Gan Yu; Jingrun Pu; Xuechen Li; Ze Tao; Zhixiang Duan; Fan Zhang; Ping Han; Hengshun Li; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Expression profiles of miRNAs in the lung tissue of piglets infected with Glaesserella parasuis and the roles of ssc-miR-135 and ssc-miR-155–3p in the regulation of inflammation - Jingyi Wang; Ping Yan; Yongchao Jia; Zhongbo Guo; Ying Guo; Ronglan Yin; Linxi Wang; Zenglei Fan; Yuanyuan Zhou; Jing Yuan; Ronghuan Yin (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Review of natural plant-derived seco-triterpenoids and derived saponins from 2020 to 2023: new compounds, distributions, diverse activities and structure–activity relationships - Xi-Fan Wei; Yi-Kun Wang; Ruo-Tong Liu; Jian-Ping Wu; Kang-Ping Xu (Phytochemistry Reviews, 2024)

Functional metabolomics characterizes the contribution of farnesoid X receptor in pyrrolizidine alkaloid-induced hepatic sinusoidal obstruction syndrome - Aizhen Xiong; Longhui Lu; Kaiyuan Jiang; Xiaoning Wang; Yan Chen; Xunjiang Wang; Wei Zhang; Yuzheng Zhuge; Wendong Huang; Lujin Li; Qi Liao; Fan Yang; et al. (Archives of Toxicology, 2024)

Current progress in umami peptides from blue foods: Preparation, screening, evaluation, synergistic effects, and taste mechanism - Li Hao; Yan Fan; Qiaoji Tian; Chaozhong Fan; Yanying Zhang; Ping Dong; Yanchao Wang; Hu Hou (Trends in Food Science & Technology, 2024)

Assessing the relative contributions, combined effects and multiscale uncertainty of future land use and climate change on water-related ecosystem services in Southwest China using a novel integrated modelling framework - Xuenan Ma; Ping Zhang; Lianwei Yang; Yuting Qi; Jiexuan Liu; Lei Liu; Xin Fan; Kang Hou (Sustainable Cities and Society, 2024)

Effects of different thawing methods on physical and physicochemical properties of frozen dough and quality of corresponding steamed bread - Fan Zhang; Jinying Guo; Peiyao Li; Fen Zhao; Xue Yang; Qiaofen Cheng; J. Stephen Elmore; Ping Wang; Can Cui (Food Chemistry, 2024)

Cellular evidence and spatial distribution of endosomal biosynthesis and autophagy in intestinal immune barrier cells of crucian carp (Carassius carassius) - Zhaoxuan Zhu; Yongchao Feng; Yuxue Pan; Shuocheng Fan; Xiangfei Meng; Yisheng Wang; Jiyue Liu; Chunyuan Dai; Jiasen Feng; Lin Peng; Qianhui Ma; Xingxing Fang; et al. (Fish & Shellfish Immunology, 2024)

Development and thermodynamic characteristics of cloud lightning channels with ultrashort-path - Lizhen Yuan; Ping Yuan; Hong Deng; Tingting An; Rubin Jiang; Liwen Xu; Fan Zhang; Yingying An (Atmospheric Research, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Production of mevalonate in Pseudomonas putida via tuning the expression of pathway gene - Linmeng Zhang; Tai-Ping Fan; Yujie Cai; Xiaohui Zheng (Systems Microbiology and Biomanufacturing, 2024)

A study on construction of a prognosis model for liver cancer based on analgesic targets and screening therapeutic drugs - Xueyan Jiang; Yaodong Ping; Yuan Chen; Benben Zhu; Rong Fu; Yiwei Hao; Lei Fan (Genes & Genomics, 2024)

Effect of rehabilitation exercise on locomotion performance of captive Bengal slow loris - Xing Bolin; Liao Linhong; Han Dongchen; Liu Jiayong; Zhao Kairui; Fan Yumai; Teng Ping; Zhang Yan; Huang Anqi; Zeng Changjun; Xie Meng; Ni Qingyong (Applied Animal Behaviour Science, 2024)

Thermostability-assisted limited proteolysis-coupled mass spectrometry for capturing drug target proteins and sites - Liu Yang; Chen-Wan Guo; Qi-Ming Luo; Zi-Fan Guo; Ling Chen; Yasushi Ishihama; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2024)

The sesquiterpenes with the COVID-19 M pro inhibitory activity from the Carpesium abrotanoides L. - Yu-Wen Fan; Zhuo-Yi Ao; Wei-Jie Zhang; Jia-Yan Chen; Xin Lian; Yong- Chen Pan; Li-Ping Chen; Jie-Wei Wu; Jie Yuan (Natural Product Research, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Numerical analysis of wet-deck slamming characteristics for trimaran section with different main-hull profiles - Jian-Yu Liu; Wen-Yang Duan; Kang-Ping Liao; Shan Ma; Wen-Bo Shao; Yi-Fan Zhang (Ocean Engineering, 2024)

Investigating the multiscale associations between urban landscape patterns and PM1 pollution in China using a new combined framework - Huimin Zhu; Ping Zhang; Ning Wang; Fengqian Zhang; Wenjie Ma; Feng Wen; Mingyao Li; Yong Wang; Xin Fan; Kang Hou; Yuanyuan Han (Journal of Cleaner Production, 2024)

A dual flow-through electrochemical system coupled electrocatalytic membrane electrode and heterogeneous electro-Fenton for organic wastewater treatment - Yuanlu Xu; Yinan Chen; Menghan Sun; Yi Zhu; Ping Tao; Xinmin Zhang; Chengwen Song; Xinfei Fan (Journal of Environmental Chemical Engineering, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

The influence of the preheated PSf substrate on COF-LZU1 layer formation and the performance for salt and pharmaceutical rejection - Fan-xin Kong; Shi-yuan Zhang; Ding-wen Zhang; Ping Xia; Jin-fu Chen (Desalination, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Synergistic signal amplification of ultrathin nanowire-like PtCoFeRuMo high-entropy nanozyme and Z-scheme WO3/ZnIn2S4 heterostructure for split-typed photoelectrochemical aptasensing of myoglobin - Fan Xu; Ben-Fang Xu; Qing-Ying Ai; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2024)

Hybrid origin and hybrid status of the endangered Ilex sanqingshanensis revealed by molecular and morphological evidence - Wei-li Liu; Dan-qi Li; Yi-ping Zou; Ming-zhuo Hao; Zhi-yong Zhang; Deng-mei Fan; Yi Yang (Plant Systematics and Evolution, 2024)

Can technological talent agglomeration improve carbon emission efficiency? Evidence from China - Ping Zhang; Yu Qian; Xuefei Wang; Fan Yang (Environment, Development and Sustainability, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Global impact of enhanced-efficiency fertilizers on vegetable productivity and reactive nitrogen losses - Zhaolong Pan; Ping He; Daijia Fan; Rong Jiang; Daping Song; Lei Song; Wei Zhou; Wentian He (Science of The Total Environment, 2024)

Salinity mixing in a tidal multi-branched estuary with huge and variable runoff - Yang Chang; Xiangyu Li; Ya Ping Wang; Knut Klingbeil; Weihua Li; Fan Zhang; Hans Burchard (Journal of Hydrology, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Plastic hinge behavior of rectangular CFRP-confined RC columns: Meso-scale modelling and formulation - Lingling Fan; Liu Jin; Ou Zhao; Jian Liang; Ping Li; Xiuli Du (Engineering Structures, 2024)

Surface reactivity versus microcracks in Ni-rich layered oxide cathodes: Which is critical for long cycle life？ - Xin Wang; Xin Zhou; Xiaohong Liu; Guilin Feng; Shuo Wang; Bin Zhang; Ping Zhang; Meihua Zuo; Wangyan Xing; Weifeng Fan; Heng Zhang; Genpin Lv; et al. (Chemical Engineering Journal, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Coupling raw material cultivation with nano-hydroxyapatite application to utilize and remediate severely Cd-containing soil - Lijie Jia; Yanli Zhou; Yunxia Su; Ping Zhao; Jingling Zhang; Wei Fan; Shengchao Yang; Guangqiang Long (Process Safety and Environmental Protection, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Resourceful utilization of combustible solid wastes throughout steelmaking processes: Recent progress and prospects - Zhiyun Ji; Dan Yu; Xiaohui Fan; Min Gan; Dan Zhang; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Xiaolong Wang; Penghui Ping (Journal of Cleaner Production, 2024)

Effect of ammonia on N migration and transformation characteristics during coal pyrolysis: Quantum chemical calculations and pyrolysis experiments - Ping Chen; Longxiang Qiao; Cheng Gong; Mingyan Gu; Kun Luo; Jianren Fan (Fuel, 2024)

Structural characteristics and antioxidant activity of Chinese giant salamander enzymatic hydrolysate-glucose conjugates induced by ultrasound Maillard reaction - Jing-jing Fu; Fan-yu He; Xing-tong Zhu; Zhen Wang; Yang-na Huang; Jin-xiu Yu; Zhi-ping Wu; Yue-wen Chen (Food Bioscience, 2024)

Intensifying the simultaneous removal of nitrogen and phosphorus of an integrated aerobic granular sludge-membrane bioreactor by Acinetobacter junii - Weifeng Liang; Biao Yang; Liying Bin; Yadong Hu; Depeng Fan; Weirui Chen; Ping Li; Bing Tang (Bioresource Technology, 2024)

Effects of metal-coupled exogenous nitrogen on the performance of supercapacitors based on biomass carbon materials - Shuai Zou; Lu Zeng; Ping Chen; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Biomass and Bioenergy, 2024)

A mapping method for emission inventory and its application in air quality modeling - Jin Fan; Mengying Shen; Tingyu Yan; Kaicheng Zhang; Tongge Zhang; Chen Gong; Xinyun Tian; Yanan Shang; Xianyu Yang; Ping Shao; Wei Tang; Maoshan Li; et al. (Atmospheric Pollution Research, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

A review on photocatalytic attribution and process of pyrolytic biochar in environment - Zhengyang E; Jianjun Liang; Ping Li; Shirong Qiang; Qiaohui Fan (Water Research, 2024)

The effect of astaxanthin on the alkalinity stress resistance of Exopalaemon carinicauda - Wenyang Li; Jiajia Wang; Jitao Li; Ping Liu; Fan Fei; Baoliang Liu; Jian Li (Science of The Total Environment, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Long-term effects of vegetation restoration and forest management on carbon pools and nutrient storages in northeastern Loess Plateau, China - Tianjiao Feng; Yulin Qi; Yufei Zhang; Dehui Fan; Tianxing Wei; Ping Wang; Saskia D. Keesstra; Artemi Cerdà (Journal of Environmental Management, 2024)

Experimental and mechanism study on NO formation characteristics and N chemical reaction mechanism in ammonia-coal co-firing - Ping Chen; Cheng Gong; Changhao Hua; Peipei Wang; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2024)

Biopolymer films incorporated with chlorogenic acid nanoparticles for active food packaging application - Kaixuan Ma; Fan Li; Taotao Zhe; Xinyu Sun; Xinyuan Zhang; Ping Wan; Huan Na; Junnan Zhao; Li Wang (Food Chemistry, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Coinoculation of arbuscular mycorrhizal fungi and rhizobia stimulates atrazine dissipation by changing the atrazine-degrading bacterial community at the soil aggregate scale - Kai Zhang; Sisi Chen; Yuan Ping; Fuqiang Song; Xiaoxu Fan; Lidong Wang; Chen Zang (Environmental Pollution, 2024)

Evolution of suspended sediment concentration profiles in the partially and periodically stratified Changjiang Estuary during dry season - Zhanhai Li; Jianjun Jia; Fan Zhang; Ya Ping Wang; Shu Gao (Estuarine, Coastal and Shelf Science, 2024)

Netrin1-carrying magnetic microspheres with magnetic field activate neurotrophin factors to guide neuronal outgrowth in vitro and in vivo - Meili Liu; Zitong An; Junwei Xu; Xiaomeng Deng; Yuchen Xiao; Ruhan A; Yeqiu Zhan; Chaojuan Yang; Ping Li; Yubo Fan (Chemical Engineering Journal, 2024)

Vehicle routing problem with time windows and carbon emissions: a case study in logistics distribution - Ping Lou; Zikang Zhou; Yuhang Zeng; Chuannian Fan (Environmental Science and Pollution Research, 2024)

Spatial distribution, source identification, and transportation paths of plutonium in the Beibu Gulf, South China Sea - Yong-jing Guan; Hua He; Kai-di Fan; Shen-zhen Wang; Zi-chen Guo; Hui-juan Wang; Liang-jia Cui; Wu Chen; Chun-ping Huang; Zhi-yong Liu; Xian-wen He; Kai-xing Guo; et al. (Marine Pollution Bulletin, 2024)

Predicting the occurrence of antagonism within ternary guanidine mixture pollutants based on the concentration ratio of components - Jian-ping Zeng; Jin Zhang; Jun-hua Hong; Yuan-fan Zhao; Jing Zhang; Ying Zhang; Xian-huai Huang; Fa-zhi Xie (Science of The Total Environment, 2024)

Seismic data, cross-section balancing, and hydrocarbon prospectivity of the western Sulaiman fold belt, northwest Pakistan - Saif-ur-Rehman K. Jadoon; Lin Ding; Ishtiaq A.K. Jadoon; Jabir Nazir; Fan Ping (Marine and Petroleum Geology, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Yucca schidigera purpurea-sourced arabinogalactan polysaccharides augments antioxidant capacity facilitating intestinal antioxidant functions - Xiangqi Fan; Xiangjun Xiao; Wei Yu; Bing Yu; Jun He; Ping Zheng; Jie Yu; Junqiu Luo; Yuheng Luo; Hui Yan; Jiangping Wang; Aimin Wu; et al. (Carbohydrate Polymers, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Modelling adaptation measures to improve maize production and reduce soil N2O emissions under climate change in Northeast China - Daijia Fan; Daping Song; Rong Jiang; Ping He; Yaoyao Shi; Zhaolong Pan; Guoyuan Zou; Wentian He (Atmospheric Environment, 2024)

Updating probable maximum precipitation for Hong Kong under intensifying extreme precipitation events - Ping Lan; Li Guo; Yaling Zhang; Guanghua Qin; Xiaodong Li; Carlos R. Mello; Elizabeth W. Boyer; Yehui Zhang; Bihang Fan (Climatic Change, 2024)

Responses of carbon and microbial community structure to soil nitrogen status vary between maize and potato residue decomposition - Linkang Chen; Ping Zhao; Chunyan Ming; Wenchun Yu; Rui Xiang; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Identifying Key Genes and Functionally Enriched Pathways in Osteoporotic Patients by Weighted Gene Co-Expression Network Analysis - Ping Fan; Xiuyuan Feng; Nan Hu; Dan Pu; Lan He (Biochemical Genetics, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Impact of sea level rise on tidal energy budget in a macro-tidal coastal bay with archipelago - Chengzhi Lu; Fan Zhang; Jianjun Jia; Ya Ping Wang (Frontiers in Marine Science, 2024)
With sea level rise (SLR), tidal nuisance flooding has become a growing threat, especially around estuaries with large tidal amplitudes. This study investigated how sea level change affects tides in Hangzhou Bay, a macro-tidal estuary with high SLR rate. By downscaling climate projections to a regional hydrodynamic model, the amplitude of primary tidal constituent (M 2 ) was predicted to increase by 0.25 m in the upper bay, where the amplitude of major diurnal tide (K 1 ) was also predicted to increase by 15%. In addition, the sensitivity of tidal amplitude to mean sea level was examined by a set of numerical simulations with different SLR. It was found that the increase of tidal amplitude is nonlinear to SLR, and the tidal amplitudes almost cease to increase when SLR is over 1.5 m. Although predictions show less amplitude changes in the lower bay, Zhoushan Archipelago around the bay mouth strongly modulates the incoming tidal energy, thus affecting the tidal amplitude in the upper bay. Energy budget analysis revealed that the complex topography, such as narrow channels, in the archipelago area leads to strong horizontal shear, which dissipates approximately 25% of total tidal energy in the bay. On the other hand, around 60% of the energy is dissipated in the bottom boundary layer. However, the bottom dissipation decreases by 4% due to reduced friction, while horizontal dissipation increases by 10% due to enhanced horizontal shear with SLR. This suggests that the strong horizontal shear in the Zhoushan archipelago region can play a more important role in the tidal energy budget in the future.

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

Enzymatic reactions throughout cultivation, processing, storage and post-processing: Progressive sculpture of tea quality - Jiali Hu; Xinyu Feng; Haizhao Song; Zhilong Hao; Shicheng Ma; Hao Hu; Yunyun Yang; Su Zhou; Yani Pan; Fangyuan Fan; Shuying Gong; Ping Chen; et al. (Trends in Food Science & Technology, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Evaluating nutrient limitation in co-culture of Chlorella pyrenoidosa and Rhodobacter sphaeroides - Xiao-Fei Shen; Ya-Ping Xu; Yi-Fan Jiang; Lin-Jun Gao; Xiao-Qin Tong; Jing Gong; Yan-Fang Yang; Raymond Jianxiong Zeng (Science of The Total Environment, 2024)

Molecular characterization, expression analysis and subcellular location of the members of STAT family from spotted seabass (Lateolabrax maculatus) - Chong Xu; Ping Wu; Qian Gao; Chuanguo Cai; Ke Fan; Jie Zhou; Lina Lei; Liangbiao Chen (Fish & Shellfish Immunology, 2024)

A novel method for predicting the emergence of toxicity interaction in ternary mixtures - Jian-Ping Zeng; Jin Zhang; Jing Zhang; Xian-huai Huang; Ying Zhang; Yuan-fan Zhao; Gui-yun Hong (Environmental Research, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Suppressing surface and bulk effect enables high efficiency solution-processed kesterite solar cells - Yunhai Zhao; Jun Zhao; Xingye Chen; Michel Cathelinaud; Shuo Chen; Hongli Ma; Ping Fan; Xianghua Zhang; Zhenghua Su; Guangxing Liang (Chemical Engineering Journal, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Mineral composition controls the stabilization of microbially derived carbon and nitrogen in soils: Insights from an isotope tracing model - Xu Wang; Chao Wang; Xianlei Fan; Lifei Sun; Changpeng Sang; Xugao Wang; Ping Jiang; Yunting Fang; Edith Bai (Global Change Biology, 2024)
Evidence is emerging that microbial products and residues (necromass) contribute greatly to stable soil organic matter (SOM), which calls for the necessity of separating the microbial necromass from other SOM pools in models. However, the understanding on how microbial necromass stabilizes in soil, especially the mineral protection mechanisms, is still lacking. Here, we incubated 13 C‐ and 15 N‐labelled microbial necromass in a series of artificial soils varying in clay minerals and metal oxides. We found the mineralization, adsorption and desorption rate constants of necromass nitrogen were higher than those of necromass carbon. The accumulation rates of necromass carbon and nitrogen in mineral‐associated SOM were positively correlated with the specific surface area of clay minerals. Our results provide direct evidence for the protection role of mineral in microbial necromass stabilization and provide a platform for simulating microbial necromass separately in SOM models.

Fluid mud induced by periodic tidal advection and fine-grained sediment settling in the Yangtze estuary - Hao Wu; Jieping Tang; Weihua Li; Fei Xing; Haifei Yang; Fan Zhang; Ya Ping Wang (Frontiers in Marine Science, 2023)
This study presents in-situ observations of fluid mud in the Yangtze Estuary via a bottom tripod. Six occurrences of periodic fluid muds (F1-F6) were observed at high slack water, with suspended sediment concentration (SSC) exceeding 10 kg/m 3 . The thickness of the fluid mud varied across the six occurrences, reaching a maximum of 0.32m. Notably, temperature and salinity anomalies were observed within the fluid mud. The formation of fluid mud was found to be influenced by turbulence, with turbulence kinetic energy (TKE) below 5×10 -4 m 2 /s 2 favoring settling as the primary cause of formation. The critical shear stress ( τ cw ) for fluid mud formation was estimated to be approximately 0.09 Pa. The formation of fluid muds during early tidal cycles was attributed to liquefaction and bed erosion resulting from strong waves. However, in most cases, the wave energy was insufficient for erosion, suggesting that advection played a role in sediment supply during the subsequent tide cycles. The increased cross-channel current velocity during flood facilitated the lateral transport of a significant amount of eroded sediment from shallow water into the channel. Due to its short duration, the fluid mud layer was entrained by the current before consolidation. Enhanced turbulence led to the breakdown of fluid mud at the early ebb. The critical τ cw for fluid mud breakdown depended on the density and duration of the fluid mud, with a maximum value of up to 0.70 Pa. The absence of the fluid mud layer during low slack water and neap tide was associated with a reduction in advection and tidal pumping, disrupting the original sediment balance between supply and demand. These data provide valuable insights into the formation and breakdown of fluid mud, contributing to estuarine hydrodynamic modeling studies and enhancing the understanding of estuary dynamics.

Porcine IGFBP3 promotes porcine circovirus type 2 replication via PERK/eIF2α mediated DNA damage - Haochun Pan; Changchao Huan; Yutong Hou; Ping Yan; Fan Yang; Luyao Jiang; Song Gao (Veterinary Microbiology, 2023)

Another thread to uncover the aging mystery of white tea: Focusing on the natural nanoparticles in tea infusion - Ruiyu Zhu; Zhen Chen; Helin Lv; Yani Pan; Xinyu Feng; Guicai Chen; Weilian Hu; Tianhua Xu; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2023)

Increased and fluctuating phosphorus nutrient availability positively affects the growth of the invasive plant Solidago canadensis - Miaomiao Cui; Bin Yang; Guangqian Ren; Piergiorgio Stevanato; Xue Fan; Ping Huang; Jianfan Sun; Daolin Du (Flora, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Electronegative graphene film based interface-chemistry regulation for stable lithium metal batteries - Ping Xie; Yumeng Peng; Xianbin Liu; Binze Yang; Fan Yang; Haijie Zhao; Sayed Y. Attia; Xiaoming Xu; Yulong Sun; Yanhong Yin; Yesheng Li; Ziping Wu (Chemical Engineering Journal, 2023)

A mesh-free finite-difference scheme for frequency-domain acoustic wave simulation with topography - Xiao-Hui Cai; Chan-Juan Huang; Tao-Ran; Xiao-Ping Fan; Heng Liu (Applied Geophysics, 2023)

Synergistic relationship and interact driving factors of pollution and carbon reduction in the Yangtze River Delta urban agglomeration, China - Min An; Meng Fan; Ping Xie (Environmental Science and Pollution Research, 2023)

Promoted iron corrosion and enhanced phosphate removal by micro-electric field driven zero-valent iron - Chunlin Fan; Bing Li; Weiquan Li; Weiting Chen; Weizhao Yin; Ping Li; Jinhua Wu (Chemosphere, 2023)

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Physiological and transcriptomic analyses reveal that phytohormone pathways and glutathione metabolism are involved in the arsenite toxicity response in tomatoes - Yingzhi Wang; Menglu Xing; Xinru Gao; Min Wu; Fei Liu; Liangliang Sun; Ping Zhang; Ming Duan; Weixin Fan; Jin Xu (Science of The Total Environment, 2023)

Studying the mechanism and impact of H2O-rich atmosphere on N oxidation during ammonia combustion and ammonia-coal co-combustion - Ping Chen; Boyu Jiang; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Chemometrics-based investigation of non-volatiles/volatiles flavor of tencha (Camellia sinensis cv. Yabukita, Longjing 43 and Baiye 1) - Qiuwen Yu; Chuangsheng Huang; Ruolan Zhu; Debiao Lu; Liping Liu; Jianhong Lai; Xinyao Zhong; Jueshan Guan; Senjie Zhou; Yilin Tong; Zipei Wang; Ping Chen; et al. (Food Research International, 2023)

Different photoreduction processes of Cr(VI) on cellulose-rich and lignin-rich biochar - Zhengyang E; Jianjun Liang; Yaqiong Dong; Qian Chao; Ping Li; Qiaohui Fan (Environmental Research, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Correction: Optimization of a 2A self-cleaving peptide-based multigene expression system for efficient expression of upstream and downstream genes in silkworm - Yuancheng Wang; Feng Wang; Sheng Xu; Riyuan Wang; Wenjing Chen; Kai Hou; Chi Tian; Fan Wang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2023)

Correction: Optimization of a 2A self-cleaving peptide-based multigene expression system for efficient expression of upstream and downstream genes in silkworm - Yuancheng Wang; Feng Wang; Sheng Xu; Riyuan Wang; Wenjing Chen; Kai Hou; Chi Tian; Fan Wang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2023)

Rab11-FIP4 interacts with ARF5 to promote cancer stemness in hepatocellular carcinoma - Feifeng Song; Qi Zhang; Xixuan Lu; Tong Xu; Qing Hu; Xiaoping Hu; Weijiao Fan; Yiwen Zhang; Ping Huang (Journal of Physiology and Biochemistry, 2023)

Seasonal Disparities of Human Health Risk and Particle-Bound Metal Characteristics Associated with Atmospheric Particles in a Fishery Harbor - Cheng-Yun Tsai; Yen-Ping Peng; Chia-Hua Lin; Ku-Fan Chen; Chia-Hsiang Lai; Pin-Hao Qiu (Archives of Environmental Contamination and Toxicology, 2023)

Three new hasubanan-type alkaloids from the Stephania longa - Rong-Xiao Lin; Lixia Fan; Xin Chen; Jundi Wu; Zheng Liu; Fang Liu; An-Ping Yang; Chenglai Xia; Hui Liu; Hong-Yuan Chen (Natural Product Research, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Development of a novel method for diagnosis of fasciolosis based on cathepsin L7 in ruminants - Jing-Zhi Gong; Yi-Min Fan; Wanzhe Yuan; Ming Pan; Dandan Liu; Jian-Ping Tao; Si-Yang Huang (Veterinary Parasitology, 2023)

Tea storage: A not thoroughly recognized and precisely designed process - Helin Lv; Xinyu Feng; Haizhao Song; Shicheng Ma; Zhilong Hao; Hao Hu; Yunyun Yang; Yani Pan; Su Zhou; Fangyuan Fan; Shuying Gong; Qiang Chu; et al. (Trends in Food Science & Technology, 2023)

Mediation of endoplasmic reticulum stress and NF-κB signaling pathway in DINP-exacerbated allergic asthma: A toxicological study with Balb/c mice - Fan Lei; Yang Wu; Chongyao Li; Biao Yan; Shaohui Chen; Qi Peng; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2023)

Photoelectrochemical degradation of TMAH by green synthesized silver modified titanate nanotube arrays - Wu-Xing Chen; Ku-Fan Chen; Ken-Ling Chang; Wei-Hsiang Chen; Chia-Hua Lin; Chia-Hung Chen; Ci-Yi Shih; Yi-Chun Chen; Yen-Ping Peng (Journal of Environmental Chemical Engineering, 2023)

Sediment exchange between southern yellow sea and Yangtze river Estuary in response to storm events - Yao Xu; Fei Xing; Jun Cheng; Fan Zhang; Hailun He; Jicai Zhang; Jianjun Jia; Ya Ping Wang (Estuarine, Coastal and Shelf Science, 2023)

Compressive stress-strain behavior and model for geometrical-similar BFRP RC square columns - Ping Li; Liu Jin; Lingling Fan; Jian Liang; Xiuli Du (Engineering Structures, 2023)

Efficient degradation of sulfadiazine by photosynthetic cyanobacteria Synechocystis sp. PCC 6803 coupling with recombinant laccase strategy - Ping Wu; Tianyouzi Hu; Liyun Sun; Jianhua Fan (Chemical Engineering Journal, 2023)

Ultrasmall IrO2 nanoparticles anchored on hollow Co-Mo multi-oxide heterostructure nanocages for efficient oxygen evolution in acid - Weiwei Han; Yang Qian; Fan Zhang; Yi He; Ping Li; Xingwang Zhang (Chemical Engineering Journal, 2023)

Formation and evolution mechanisms of a destructive-wind-producing thunderstorm in Shanghai - Yanan Liu; Fan Ping; Chenchen Ding; Xiaochen Zhang (Atmospheric Research, 2023)

Human lactate dehydrogenase and malate dehydrogenase possess the catalytic properties to produce aromatic α-hydroxy acid - Litong Wang; Tai-Ping Fan; Mei Wang; Yajun Bai; Xiaohui Zheng; Yujie Cai (Systems Microbiology and Biomanufacturing, 2023)

Characterization of acid-resistant aldo–keto reductases capable of asymmetric synthesis of (R)-CHBE from Lactobacillus plantarum DSM20174 - Jiufeng Zhu; Yajun Bai; Tai-Ping Fan; Xiaohui Zheng; Yujie Cai (Systems Microbiology and Biomanufacturing, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

Vibration responses of the metro station induced by various train operations under unilateral deep excavation - Feicong Zhou; Wenhao Fan; Jiayong Lin; Ping Zhou; Mao Chen; Zhijie Wang (Transportation Geotechnics, 2023)

Study on the influence mechanism of mineral Ca on NO reduction in the high temperature oxygen-lean zone of ammonia-coal co-combustion - Xiangyong Huang; Ping Chen; Ying Wang; Mingyan Gu; Yao Fang; Jianren Fan; Yi Wang (Fuel, 2023)

Multi-element and metabolite characterization of commercial Phyllanthi Fructus with geographical authentication and quality evaluation purposes - Qin Guan; Tingting Pu; Zhongyu Zhou; Min Fan; Conglong Xia; Yinglin Liu; Ping Zhou; Wei Yang; Baozhong Duan (Food Control, 2023)

Hierarchical microsphere Flower-like SnIn4S8 with active sulfur sites for adsorption and removal of mercury from coal-fired flue gas - Yuanqin Xue; Xu Fang; Haoyu Jiang; Jiang Wu; Hailong Liu; Xin Li; Ping He; Fangqin Li; Yongfeng Qi; Qihang Gao; Yilin Fan (Chemical Engineering Journal, 2023)

Four new stilbenes and one new flavonoid with potential antibacterial and anti-SARS-CoV-2 activity from Cajanus cajan - Jia-Yan Chen; Xin Lian; Yu-Wen Fan; Zhuo-Yi Ao; Wei-Jie Zhang; Yong-Chen Pan; Li-Ping Chen; Jie Yuan; Jie-Wei Wu (Journal of Natural Medicines, 2023)

Isolation and identification of Bacillus and abilities of 3 functional strains to control powdery mildew and promote seedling growth of Malus sieversii - Bin Liu; Yanrong Xu; Shida Ji; Ping Zhang; Huifang Zhang; Jing Han; Haijuan Fan; Jinjie Wang; Jinyu Qi; Yue Ma; Zhihua Liu (European Journal of Plant Pathology, 2023)

Research advances in application of mainstream anammox processes: Roles of quorum sensing and microbial metabolism - Xue-Ping Wang; Qian Wu; Xin Wang; Nian-Si Fan; Ren-Cun Jin (Chemosphere, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

Remediating petroleum hydrocarbons in highly saline–alkali soils using three native plant species - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yanhong Liu; Rong Ma; Ruijie Li; Leiping Shi (Journal of Environmental Management, 2023)

NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

A time-series InSAR processing chain for wide-area geohazard identification - Zhike Zhang; Ping Duan; Jia Li; Deying Chen; Kang Peng; Chengpeng Fan (Natural Hazards, 2023)

Chromoblastomycosis Caused by Cladosporium tenuissimum in an Elderly Man - Yan-Ping Yang; Ci-Juan Zhong; Shu-Jun Yin; Yi-Ming Fan (Mycopathologia, 2023)

Distribution, sources and risk assessment of polycyclic aromatic hydrocarbons in surface sediments from the Yellow Sea coast, China - Daolai Zhang; YaoYao Wang; Xuejun Jiang; Ke Cao; Ping Yin; Zongshan Zhao; Ying Fan; Na Liu (Marine Pollution Bulletin, 2023)

Thermal preconditioning can reduce the incidence of intraoperatively acquired pressure injuries - Ping Hou; Huiping Xue; Shuwen Chang; Ping Xie; Yajie Chen; Yanwei Wang; Daiji Miura; Jianglin Fan; Jingyan Liang; Akio Kitayama; Fang Fang; Haijuan Yuan; et al. (Journal of Thermal Biology, 2023)

Heavy metals immobilization of ternary geopolymer based on nickel slag, lithium slag and metakaolin - Jinyuan Fan; Jiahao Yan; Mengya Zhou; Yuan Xu; Yuwei Lu; Ping Duan; Yingcan Zhu; Zuhua Zhang; Wengui Li; Aiguo Wang; Daosheng Sun (Journal of Hazardous Materials, 2023)

Face Stability of Tunnel in Multi-stratum: Limit Analysis and Numerical Simulation - Yanbo Chang; Ping Cao; Jian Zhang; Zhi Fan; Weiping Xie; Zhizhen Liu; Huijuan Deng; Qingxiong Zhao (Geotechnical and Geological Engineering, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

Attapulgite amendment favors the utilization of high cadmium-contaminated soil for Erigeron breviscapus cultivation - Lijie Jia; Wei Fan; Peili Wang; Yu Chen; Ping Zhao; Shengchao Yang; Guangqiang Long (Chemosphere, 2023)

Interactions between micaceous minerals weathering and cesium adsorption - Wei Wang; Leiping Shi; Hanyu Wu; Zhe Ding; Jianjun Liang; Ping Li; Qiaohui Fan (Water Research, 2023)

Fine-tuning immunity against cancer: the emergence of engineered commensal microbiota - Shi-Jun He; Fan Yang; Jian-Ping Zuo; Ze-Min Lin (Science Bulletin, 2023)

Formation and transport of fluid mud triggered by typhoon events in front of the subaqueous Changjiang Delta - Jieping Tang; Hao Wu; Fei Xing; Fan Zhang; Bixuan Tang; Gaocong Li; Ya Ping Wang (Marine Geology, 2023)

Confined self-assembly of S, O co-doped GCN short nanotubes/EG composite towards HMIs electrochemical detection and removal - Jue Wang; Kan Kan; Ping Yu; Yihe Fan; Jiahui Fan; Lin Jiang; Fangjie Qin; Keying Shi (Journal of Hazardous Materials, 2023)

Highly efficient removal of phosphonates by ferrate-induced oxidation coupled with in situ coagulation - Wen-Yuan Fan; Xin Zhang; Pu-Can Guo; Guo-Ping Sheng (Journal of Hazardous Materials, 2023)

Highly sensitive detection of thiram residues on fruit peel surfaces using a filter paper-based SERS sensor with AgNWs@ZIF-8 - Nuan Xu; Zhenhua Tang; Yan-Ping Jiang; Junlin Fang; Li Zhang; Xiaofang Lai; Qi-Jun Sun; Jing-Min Fan; Xin-Gui Tang; Qiu-Xiang Liu; Ji-Kang Jian (Journal of Environmental Chemical Engineering, 2023)

Mechanism analysis of fuel-N oxidation during ammonia-coal co-combustion: Influence of H2O - Ping Chen; Cheng Gong; Changhao Hua; Mingyan Gu; Boyu Jiang; Jianren Fan; Yi Wang (Fuel, 2023)

Combined effect of konjac glucomannan addition and ultrasound treatment on the physical and physicochemical properties of frozen dough - Peng Lu; Jinying Guo; Jiawei Fan; Ping Wang; Xiang Yan (Food Chemistry, 2023)

Pu’ er raw tea extract alleviates DSS-induced colitis in mice by restoring intestinal barrier function and maintaining gut microbiota homeostasis - Su Zhou; Jiaying Yang; Yani Pan; Xinyu Feng; Hao Hu; Shicheng Ma; Cansong Ou; Fangyuan Fan; Shuying Gong; Yuefei Wang; Ping Chen; Qiang Chu (Food Bioscience, 2023)

m6A-dependent mevalonate kinase in juvenile hormone synthesis pathway regulates the diapause process of bivoltine silkworm (Bombyx mori) - Yan-Hua Chen; Tao Jiang; Ayinuer Yasen; Bing-Yan Fan; Juan Zhu; Mei-Xian Wang; Ping Qian; Xing-Jia Shen (Molecular Biology Reports, 2023)

Optimizing human endometrial mesenchymal stem cells for maximal induction of angiogenesis - Jie Zhang; Huifang Song; Xuemei Fan; Sheng He; Wenjuan Yin; Zexu Peng; Xiaoyan Zhai; Kun Yang; Hui Gong; Zhijun Wang; Yi Ping; Sanyuan Zhang; et al. (Molecular and Cellular Biochemistry, 2023)

Pollution evaluation and source identification of heavy metals in soil around steel factories located in Lanshan District, Rizhao City, eastern China - Ping Wang; Weihua Huang; Fuyue Ren; Deqiang Fan (Environmental Monitoring and Assessment, 2023)

Improving potato productivity and mitigating nitrogen losses using enhanced-efficiency fertilizers: A global meta-analysis - Zhaolong Pan; Daijia Fan; Rong Jiang; Naeem Abbasi; Daping Song; Guoyuan Zou; Dan Wei; Ping He; Wentian He (Agriculture, Ecosystems & Environment, 2023)

Fermented foods and metabolic outcomes in diabetes and prediabetes: A systematic review and meta-analysis of randomized controlled trials - Xiao-Feng Zhang; Yue Qi; Yong-Ping Zhang; Jin-Lan Deng; Xiao-Li Chen; Ruo-Nan Li; Qi-Lun Zhou; Jian-Ming Fan (Critical Reviews in Food Science and Nutrition, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Novel caffeic acid grafted chitosan-sodium alginate microcapsules generated by microfluidic technique for the encapsulation of bioactive peptides from silkworm pupae - Xiao-Meng Xun; Zhi-Ang Zhang; Zi-Xuan Yuan; Kamila Tuhong; Cheng-Hai Yan; Yu-Fan Zhan; Guo-Ping Kang; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Low-dose ionizing radiation: Effects on the proliferation and migration of lens epithelial cells via activation of the Wnt/β-catenin pathway - Ping Wang; Yu-Wen Li; Xue Lu; Ya Liu; Xue-Lei Tian; Ling Gao; Qing-Jie Liu; Li Fan; Mei Tian (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Reduced and deep application of controlled-release urea maintained yield and improved nitrogen-use efficiency - Kaibo Hu; Ping Zhao; Kaixian Wu; Hongli Yang; Qingxia Yang; Maopan Fan; Guangqiang Long (Field Crops Research, 2023)

Development and challenges of deep eutectic solvents for cathode recycling of end-of-life lithium-ion batteries - Yuxin Fan; Yuelin Kong; Pinxian Jiang; Guohua Zhang; Jianlong Cong; Xinyue Shi; Yukun Liu; Ping Zhang; Renyuan Zhang; Yunhui Huang (Chemical Engineering Journal, 2023)

Mathematical Model of Two-Phase Spontaneous Imbibition with Dynamic Contact Angle - Lei Zhang; Jingjing Ping; Bo Tang; Lixin Kang; Gloire Imani; Yongfei Yang; Hai Sun; Junjie Zhong; Jun Yao; Dongyan Fan (Transport in Porous Media, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

Recent advances on white tea: Manufacturing, compositions, aging characteristics and bioactivities - Su Zhou; Jinming Zhang; Shicheng Ma; Cansong Ou; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; Qiang Chu (Trends in Food Science & Technology, 2023)

Research on the ozone formation sensitivity indicator of four urban agglomerations of China using Ozone Monitoring Instrument (OMI) satellite data and ground-based measurements - Yuping Chen; Meiyuan Wang; Yijuan Yao; Chunling Zeng; Wei Zhang; Hui Yan; Ping Gao; Liya Fan; Daiqi Ye (Science of The Total Environment, 2023)

La2Ti2O7 nanosheets modified by Pt quantum dots for efficient NO removal avoiding NO2 secondary pollutant - Li Lv; Hong-Dan Yang; Qi-Wen Chen; Huiqing Fan; Jian-Ping Zhou (Environmental Research, 2023)

Automatic-degradable Mo-doped W18O49 based nanotheranostics for CT/FL imaging guided synergistic chemo/photothermal/chemodynamic therapy - Yilong Tian; Wenhui Yi; Qiuya Shao; Minghai Ma; Lei Bai; Rundong Song; Ping Zhang; Jinhai Si; Xun Hou; Jinhai Fan (Chemical Engineering Journal, 2023)

Role of meteorology-driven regional transport on O3 pollution over the Chengdu Plain, southwestern China - Yu Lei; Kai Wu; Xiaoling Zhang; Ping Kang; Yunsong Du; Fumo Yang; Jin Fan; Jingwen Hou (Atmospheric Research, 2023)

In Vitro Antifungal Activity of Azoles and Other Antifungal Agents Against Pathogenic Yeasts from Vulvovaginal Candidiasis in China - Siyue Kan; Nana Song; Qiuyu Pang; Huan Mei; Hailin Zheng; Dongmei Li; Fan Cui; Guixia Lv; Ruifang An; Ping Li; Zhengai Xiong; Shangrong Fan; et al. (Mycopathologia, 2023)

Effect of CDM3 on co-culture of human-induced pluripotent stem cells with Matrigel-covered polycaprolactone to prepare cardiac patches - Yue Dai; Fan Zhou; Jianwei Zheng; Junsheng Mu; Ping Bo; Bin You (In Vitro Cellular & Developmental Biology - Animal, 2023)

A novel label-free dual-mode aptasensor based on the mutual regulation of silver nanoclusters and MoSe2 nanosheets for reliable detection of ampicillin - Pengfei Fan; Xin Qian; Qianji Li; Ping Jiang; Qian Wu; Guang Huang; Zhan Zhang; Lei Li (Analytica Chimica Acta, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Ambient temperature and ambulatory blood pressure: An hourly–level, longitudinal panel study - Ping Fan; Xiaowei Xue; Jialu Hu; Qingxia Qiao; Tingting Yin; Xiaoling Yang; Xiyin Chen; Yuemei Hou; Renjie Chen (Science of The Total Environment, 2023)

Combining the advantages of Rhizophagus intraradices and Serendipita indica to reduce the risk of Cd on soybean safety and environmental pollution - Xiaohui Wang; Xiaoxu Fan; Wei Chang; Kun Li; Mengmeng Zhang; Yuan Ping; Fuqiang Song (Rhizosphere, 2023)

Revealing the influence of oxygen-containing functional groups on mercury adsorption via density functional theory and multiple linear regression analysis - Hai Zhang; Huang Qin; Xin Wang; Yilin Pan; Ping He; Jiang Wu; Weidong Fan (Fuel, 2023)

Influence mechanism of ammonia mixing on NO formation characteristics of pulverized coal combustion and N oxidation in ammonia-N/coal-N - Ping Chen; Changhao Hua; Boyu Jiang; Mingyan Gu; Zhenling Ge; Meng Zhang; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Analysis on Precipitation Efficiency of the “21.7” Henan Extremely Heavy Rainfall Event - Lei Yin; Fan Ping; Jiahua Mao; Shuanggen Jin (Advances in Atmospheric Sciences, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

A comprehensive review on mixotrophic denitrification processes for biological nitrogen removal - Jintao Zhang; Chunzhen Fan; Min Zhao; Zhiquan Wang; Shunfeng Jiang; Zhan Jin; Ke Bei; Xiangyong Zheng; Suqing Wu; Ping Lin; Huanyi Miu (Chemosphere, 2023)

Novel economy and carbon emissions prediction model of different countries or regions in the world for energy optimization using improved residual neural network - Yongming Han; Lian Cao; Zhiqiang Geng; Weiying Ping; Xiaoyu Zuo; Jinzhen Fan; Jing Wan; Gang Lu (Science of The Total Environment, 2023)

Effect of etching and reduction time on the structure, performance, and stability of GO-based membrane for water purification - Fan-xin Kong; Lian You; Jia-mei Cao; Qian Liu; Ping Xia; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2023)

Using BHR to detect coal seam interface in coal mine - Bici Jiang; Jianyuan Cheng; Ping Li; Tao Fan (Journal of Applied Geophysics, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Comparison of Artificial Feed and Natural Food by the Growth and Blood Biochemistry in Chinese Sturgeon Acipenser sinensis - Yueping Zheng; Jiehao Liu; Jianan Xu; Houyong Fan; Youji Wang; Ping Zhuang; Menghong Hu (Fishes, 2023)
As an endangered animal species, the Chinese sturgeon (Acipenser sinensis) has been artificially cultured during recent years. In the present experiment, the performance of a common formulated feed and a mixed natural feed on the growth and blood physiology of Chinese sturgeon were compared during one year of indoor culture. In terms of specific growth rate, the formulated diet group showed a higher value (4.2%) compared with the natural food group (−1.8%) during one year of indoor culture. Alanine aminotransferase activities of the sturgeons in formulated diet group was significantly higher than that in the natural food group throughout whole experiment period (p

Photoreduction behavior of Cr(VI) on oxidized carbon nanoparticles: From photocatalytic efficiency to oxygenated groups - Zhe Ding; Wentao Zhang; Jianjun Liang; Shirong Qiang; Wei Wang; Ping Li; Qiaohui Fan (Chemosphere, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Investigation of the relationship between MBP gene polymorphisms and delayed encephalopathy after acute carbon monoxide poisoning - Fan Zhang; Jiao Zeng; Xiaoli Zhang; Jiapeng Gu; Yongkai Han; Ping Zhang; Wenqiang Li; Renjun Gu (NeuroToxicology, 2023)

Catalysts for gaseous organic sulfur removal - Yuxuan Xie; Jiacheng Bao; Xin Song; Xin Sun; Ping Ning; Chi Wang; Fei Wang; Yixing Ma; Maohong Fan; Kai Li (Journal of Hazardous Materials, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

A simple model for predicting dispersion characteristics of high-temperature airflow and particle distribution during smelting process in a thermally stratified foundry shop - Fan Liu; Hua Qian; Jianchao Ma; Ping He (Energy and Buildings, 2023)

Photo-induced self-reduction enabling ultralow threshold voltage energy-conservation electrochromism - Zhiyuan Bai; Ran Li; Lu Ping; Qingchao Fan; Ziqiu Lu; Chengyi Hou; Qinghong Zhang; Yaogang Li; Kerui Li; Xi Ling; Hongzhi Wang (Chemical Engineering Journal, 2023)

Defects passivation by solution-processed titanium doping strategy towards high efficiency kesterite solar cells - Umar Farooq; Usman Ali Shah; Muhammad Ishaq; Ju-Guang Hu; Shehzad Ahmed; Shuo Chen; Zhuang-Hao Zheng; Zheng-Hua Su; Ping Fan; Guang-Xing Liang (Chemical Engineering Journal, 2023)

Engineering ZnSn(OH)6 with ternary active sites-directed hydroxyl vacancies for robust deep C6H6 photo-oxidation: Experiment and DFT calculations - Yuhan Li; Bangfu Chen; Ping Ouyang; Youyu Duan; Wee-Jun Ong; Fan Dong (Chemical Engineering Journal, 2023)

Clioquinol induces autophagy by down-regulation of calreticulin in human neurotypic SH-SY5Y cells - Xiaoguang Lv; Zheyu Fan; Fangqi Cao; Wenbin Liu; Zhiwei Huang; Ping Shi (Chemico-Biological Interactions, 2023)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Oxygen-containing groups in cellulose and lignin biochar: their roles in U(VI) adsorption - Yongzhong Feng; Xiaoyi Qiu; Zhuolin Tao; Zhengyang E; Jiayu Song; Yaqiong Dong; Jianjun Liang; Ping Li; Qiaohui Fan (Environmental Science and Pollution Research, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Theoretical analysis on influence factors of anchor cable internal force under over-excavation considering earth berm - Jiayong Lin; Feicong Zhou; Wenhao Fan; Mao Chen; Jinyi Li; Yifan Jiang; Ming Lin; Ping Zhou; Zhijie Wang (Arabian Journal of Geosciences, 2022)

Investigating and predicting spatiotemporal variations in vegetation cover in transitional climate zone: a case study of Gansu (China) - Qing He; Kwok Pan Chun; Bastien Dieppois; Liang Chen; Ping Yu Fan; Emir Toker; Omer Yetemen; Xicai Pan (Theoretical and Applied Climatology, 2022)
Vegetation ecosystems are sensitive to large-scale climate variability in climate transition zones. As a representative transitional climate zone in Northwest China, Gansu is characterized by a sharp climate and vegetation gradient. In this study, the spatiotemporal variations of vegetation over Gansu are characterized using the satellite-based normalized difference vegetation index (NDVI) observations during 2000–2020. Results demonstrate that a significant greening trend in vegetation over Gansu is positively linked with large-scale climate factors through modulating the water and energy dynamics. As a climate transition zone, the northern water-limited and southern energy-limited regions of Gansu are affected by water and energy dynamics, differently. In the water-limited region, a weakening Asian monsoon along with colder Central Pacific (CP) and warmer North Pacific (NP) Oceans enhances prevailing westerlies which bring more atmospheric moisture. The enhanced atmospheric moisture and rising temperature promote the local vegetation growth. In contrast, large-scale climate variations suppress the southwest monsoon moisture fluxes and reduce precipitation in southern energy-limited regions. In these energy-limited regions, temperature has more effects on vegetation growth than precipitation. Therefore, the greenness of vegetation is because of more available energy from higher temperatures despite overall drying conditions in the region. Based on the above mechanism, future scenarios for climate impacts on vegetation cover over Gansu region are developed based on the two latest generation from coupled climate models (Coupled Model Intercomparison Project Phase 5 and Phase 6; CMIP5 and CMIP6). In the near-term future (2021–2039), the vegetation is likely to increase due to rising temperature. However, the vegetation is expected to decrease in a long-term future (2080–2099) when the energy-limited regions become water-limited due to increasing regional temperatures and lowering atmospheric moisture flux. This study reveals an increasing desertification risk over Gansu. Similar investigations will be valuable in climate transition regions worldwide to explore how large-scale climate variability affects local ecological services under different future climate scenarios.

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

Overexpression of PYGO1 promotes early cardiac lineage development in human umbilical cord mesenchymal stromal/stem cells by activating the Wnt/β-catenin pathway - Jie Shen; Xiushan Wu; Ping Zhu; Jian Zhuang; Bin Qin; Fang Sun; Wuzhou Yuan; Xiongwei Fan; Zhigang Jiang; Fang Li; Yongqing Li; Yuequn Wang; et al. (Human Cell, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

The α5-nAChR/PD-L1 axis facilitates lung adenocarcinoma cell migration and invasion - Ping Zhu; Guiyu Kang; Yang Jiao; Chengzhi Gui; Huiping Fan; Xiangying Li; Yanfei Jia; Lulu Zhang; Xiaoli Ma (Human Cell, 2022)

Impact of environmental regulation on green total factor productivity: a new perspective of green technological innovation - Min Fan; Ping Yang; Qing Li (Environmental Science and Pollution Research, 2022)

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Adventitious bud regeneration and Agrobacterium tumefaciens-mediated genetic transformation of Eucalyptus urophylla × E. tereticornis interspecific hybrid - Xiaoping Wang; Ping Luo; Zhenfei Qiu; Xiaodan Li; Bingshan Zeng; Chunjie Fan (In Vitro Cellular & Developmental Biology - Plant, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Flexural performances of pre-stressed concrete piles reinforced with hybrid BFRP and steel bars - Ping Wu; Yang Guo; Dayong Zhu; Weiliang Jin; Chack-fan Lee (European Journal of Environmental and Civil Engineering, 2022)

A bi-scale assessing framework for aesthetic ecosystem services of villages in a world heritage site - Yin-ping Ding; Zhi-lin Liu; Yuan-mei Jiao; Qiu-e Xu; Kan-feng Zhang; Cheng-jing Liu; Fan Chen (Journal of Mountain Science, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Necrostatin-1 Relieves Learning and Memory Deficits in a Zebrafish Model of Alzheimer’s Disease Induced by Aluminum - Xiaocheng Gao; Ping Zhang; Jianping Chen; Lan Zhang; Nan Shang; Jin Chen; Rong Fan; Yanhong Wang; Tao Huang; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2022)

Correction to: Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2022)

Tropical tall forests are more sensitive and vulnerable to drought than short forests - Liyang Liu; Xiuzhi Chen; Philippe Ciais; Wenping Yuan; Fabienne Maignan; Jin Wu; Shilong Piao; Ying‐Ping Wang; Jean‐Pierre Wigneron; Lei Fan; Pierre Gentine; Xueqin Yang; et al. (Global Change Biology, 2022)
Our limited understanding of the impacts of drought on tropical forests significantly impedes our ability in accurately predicting the impacts of climate change on this biome. Here, we investigated the impact of drought on the dynamics of forest canopies with different heights using time‐series records of remotely sensed Ku‐band vegetation optical depth (Ku‐VOD), a proxy of top‐canopy foliar mass and water content, and separated the signal of Ku‐VOD changes into drought‐induced reductions and subsequent non‐drought gains. Both drought‐induced reductions and non‐drought increases in Ku‐VOD varied significantly with canopy height. Taller tropical forests experienced greater relative Ku‐VOD reductions during drought and larger non‐drought increases than shorter forests, but the net effect of drought was more negative in the taller forests. Meta‐analysis of in situ hydraulic traits supports the hypothesis that taller tropical forests are more vulnerable to drought stress due to smaller xylem‐transport safety margins. Additionally, Ku‐VOD of taller forests showed larger reductions due to increased atmospheric dryness, as assessed by vapor pressure deficit, and showed larger gains in response to enhanced water supply than shorter forests. Including the height‐dependent variation of hydraulic transport in ecosystem models will improve the simulated response of tropical forests to drought.

Microporous modified atmosphere packaging to extend shelf life of fresh foods: A review - Ping Qu; Min Zhang; Kai Fan; Zhimei Guo (Critical Reviews in Food Science and Nutrition, 2022)

Constitutive expression of tyrosine phenol-lyase from Erwinia herbicola in Escherichia coli for l-DOPA production - Mengqing Tang; Yajun Bai; Tai-Ping Fan; Xiaohui Zheng; Yujie Cai (Systems Microbiology and Biomanufacturing, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Synthesis and evaluation of mycophenolic acid derivatives as potential anti-Toxoplasma gondii agents - Fan-Fan Shang; Mei-Yuan Wang; Jiang-Ping Ai; Qing-Kun Shen; Hong-Yan Guo; Chun-Mei Jin; Fen-Er Chen; Zhe-Shan Quan; Lili Jin; Changhao Zhang (Medicinal Chemistry Research, 2021)

Evaluation of Parametric and Nonparametric Algorithms for the Estimation of Suspended Particulate Matter in Turbid Water using Gaofen-1 Wide Field-of-view Sensors - Yao Liu; Jie-Ping Fan; Hui Jiang (Journal of the Indian Society of Remote Sensing, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

Updated taxonomy of Chinese Phylloporus (Boletaceae, Boletales): six new taxa and four redescribed species - Lu-Ling Wu; Zhi-Qun Liang; Ming-Sheng Su; Yu-Guang Fan; Ping Zhang; Shuai Jiang; Yan-Liu Chen; Yan-Jia Hao; Nian-Kai Zeng (Mycological Progress, 2021)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Characterization and genome sequence of the genetically unique Escherichia bacteriophage vB_EcoM_IME392 - Yunjia Hu; Shanwei Tong; Ping Li; Xiaoping An; Lihua Song; Huahao Fan; Yigang Tong (Archives of Virology, 2021)

Drought disaster risk management based on optimal allocation of water resources - Xiao Liu; Ping Guo; Qian Tan; Fan Zhang; Yan Huang; Youzhi Wang (Natural Hazards, 2021)

Effect on simultaneous removal of ammonia, nitrate, and phosphorus via advanced stacked assembly biological filter for rural domestic sewage treatment - Ziyun Fan; Zhiwei Liang; Ancheng Luo; Yunlong Wang; Yuanyuan Ma; Yi Zhao; Xiansheng Lou; Ruijie Jia; Yan Zhang; Shaowei Ping (Biodegradation, 2021)

Degradation of octylphenol polyethoxylates with a long ethoxylate chain using the laccase-mediated systems - Dan Wang; Jiangfei Lou; Jin Xu; Jiugang Yuan; Qiang Wang; Ping Wang; Xuerong Fan (Environmental Science and Pollution Research, 2021)

Using seismic sedimentology in delineating a distributary channel type shallow-water lacustrine delta: first member of the Cretaceous Yaojia Formation in Changling area, South of Songliao Basin - Jun Wang; Kai Zeng; Bowen Wu; Jianzheng Ji; Zhidong Bao; Bin Cheng; Hongjing Zhang; Ping Xiong; Fan Diao (Arabian Journal of Geosciences, 2021)

Co-seismic landslide mapping using Sentinel-2 10-m fused NIR narrow, red-edge, and SWIR bands - Ping Lu; Wenyang Shi; Qunming Wang; Zhongbin Li; Yuanyuan Qin; Xuanmei Fan (Landslides, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Cytotoxic meroterpenoids from the marine sponge Dactylospongia elegans - Hao-Bing Yu; Zi-Fei Yin; Bin-Bin Gu; Jian-Peng Zhang; Shu-Ping Wang; Fan Yang; Hou-Wen Lin (Natural Product Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

First report of grapevine Cabernet Sauvignon reovirus from grapevines in China - Xu Dong Fan; Ya Feng Dong; Zun Ping Zhang; Fang Ren; Guo Jun Hu (Journal of Plant Pathology, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Transgenic eukaryotic microalgae as green factories: providing new ideas for the production of biologically active substances - Qianwen Shi; Cheng Chen; Wei Zhang; Ping Wu; Meng Sun; Hui Wu; Haizhen Wu; Pengcheng Fu; Jianhua Fan (Journal of Applied Phycology, 2021)

Systematic analysis to identify transcriptome-wide dysregulation of Alzheimer’s disease in genes and isoforms - Cong Fan; Ken Chen; Jiaxin Zhou; Ping-pui Wong; Dan He; Yiqi Huang; Xin Wang; Tianze Ling; Yuedong Yang; Huiying Zhao (Human Genetics, 2021)

Neonatal Sevoflurane Exposure Impairs Learning and Memory by the Hypermethylation of Hippocampal Synaptic Genes - Xin-Yu Fan; Guang Shi; Ping Zhao (Molecular Neurobiology, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

First report of grapevine enamovirus 1 in grapevine in China - Fang Ren; Zun Ping Zhang; Xu Dong Fan; Guo Jun Hu; Ya Feng Dong (Journal of Plant Pathology, 2021)

Is urban spontaneous vegetation rich in species and has potential for exploitation? - A case study in Baoji, China - Ling Qiu; Ling Zhu; Ping Chang; Jialei Wang; Junxi Fan; Tian Gao (Plant Biosystems, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Inversion analysis of the shear strength parameters for a high loess slope in the limit state - Xiao-yan Lin; Lin-fan Zhang; Ze Yang; Ping Li; Tong-lu Li (Journal of Mountain Science, 2021)

Evaluation of crustal inhomogeneity parameters in the southern Longmenshan fault zone and adjacent regions - Xiao-Ping Fan; Yi-Cheng He; Cong-Jie Yang; Jun-Fei Wang (Journal of Seismology, 2020)
Broadband teleseismic waveform data from 13 earthquakes recorded by 70 digital seismic stations were selected to evaluate the inhomogeneity parameters of the crustal medium in the southern Longmenshan fault zone and its adjacent regions using the teleseismic fluctuation wavefield method. Results show that a strong inhomogeneity exists beneath the study region, which can be divided into three blocks according to its structure and tectonic deformation features. These are known as the Sichuan-Qinghai Block, the Sichuan-Yunnan Block, and the Mid-Sichuan Block. The velocity fluctuation ratios of the three blocks are approximately 5.1%, 3.6%, and 5.1% in the upper crust and 5.1%, 3.8%, and 4.9% in the lower crust. The inhomogeneity correlation lengths of the three blocks are about 10.1 km, 14.0 km, and 10.7 km in the upper crust and 11.8 km, 17.0 km, and 11.8 km in the lower crust. The differences in the crustal medium inhomogeneity beneath the Sichuan-Yunnan Block, the Sichuan-Qinghai Block, and the Mid-Sichuan Block may be related to intensive tectonic movement and material flow in the crust and upper mantle.

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

Enzymatic hydroxylation of L-pipecolic acid by L-proline cis-4-hydroxylases and isomers separation - Fan Lu; Jiao Chen; Hai Ye; Hongli Wu; Feng Sha; Fujun Huang; Fei Cao; Ping Wei (Biotechnology Letters, 2020)

Novel ACADVL variants resulting in mitochondrial defects in long-chain acyl-CoA dehydrogenase deficiency - Ting Chen; Fan Tong; Xiao-yu Wu; Ling Zhu; Qiu-zi Yi; Jing Zheng; Ru-lai Yang; Zheng-yan Zhao; Xiao-hui Cang; Qiang Shu; Ping-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2020)

Vicissitudes experienced by the oldest urban center in Bangladesh in relation to the migration of the Brahmaputra River - Gang Hu; Ping Wang; Sufi Mostafizur Rahman; Dehong Li; Muhammad Mahbubul Alam; Jiafu Zhang; Zhengyao Jin; Anchuan Fan; Jie Chen; Aimin Zhang; Wenqing Yang (Journal of Quaternary Science, 2020)
Bangladesh is one of the most densely populated countries in the world. There are 57 trans‐frontier rivers in the country, the widest being the Brahmaputra River. The river's channels have frequently changed course, but the relationship between such river migrations and human settlement patterns has remained unstudied. In this paper, optically stimulated luminescence and radiocarbon dating techniques were applied to sedimentary and organic materials in the oldest urban center (Wari‐Bateshwar) in Bangladesh. The results showed that the landscape around the urban center was dominated by floodplain and peatland facies between 7.9–7.6 and 4.7–1.6 ka, respectively. Humans occupied this area at ~3.2 ka, and manufactured delicate semi‐precious gemstone beads between ~2.4 and 1.8 ka. The urban center might be the same as an important city of the Gangaridai described in historical records. Due to fluvial migration at ~1.8 ka, the area surrounding the urban center was covered by fluvial sand. Humans might have been forced to abandon the urban center, leading to the bead processing technology in Bangladesh being lost forever.

A field pilot-scale study on heavy metal-contaminated soil washing by using an environmentally friendly agent—poly-γ-glutamic acid (γ-PGA) - Yen-Ping Peng; Yu-Chen Chang; Ku-Fan Chen; Ching-Hsiang Wang (Environmental Science and Pollution Research, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Role of delta‐front erosion in sustaining salt marshes under sea‐level rise and fluvial sediment decline - Shi Lun Yang; Xiangxin Luo; Stijn Temmerman; Matthew Kirwan; Tjeerd Bouma; Kehui Xu; Saisai Zhang; Jiqing Fan; Benwei Shi; Haifei Yang; Ya Ping Wang; Xuefa Shi; et al. (Limnology and Oceanography, 2020)
Accelerating sea‐level rise and decreasing riverine sediment supply are widely considered to lead to global losses of deltaic marshes and their valuable ecosystem services. However, little is known about the degree to which the related erosion of the seaward delta front can provide sediments to sustain salt marshes. Here, we present data from the mesomacrotidal Yangtze Delta demonstrating that marshes have continued to accrete vertically and laterally, despite rapid relative sea‐level rise (∼10 mm yr −1 ) and a > 70% decrease in the Yangtze River sediment supply. Marsh progradation has decelerated at a lower rate than fluvial sediment reduction, suggesting an additional source of sediment. We find that under favorable conditions (e.g., a mesomacrotidal range, strong tidal flow, flood dominance, sedimentary settling lag/scour lag effects, and increasing high‐tide level), delta‐front erosion can actually supply sediment to marshes, thereby maintaining marsh accretion rates in balance with relative sea‐level rise. Comparison of global deltas illustrates that the ability of sediment remobilization to sustain marshes depends on coastal processes and varies by more than an order of magnitude among the world's major deltas.

Aluminum-Induced Cognitive Impairment and PI3K/Akt/mTOR Signaling Pathway Involvement in Occupational Aluminum Workers - Nan Shang; Ping Zhang; Shuo Wang; Jianping Chen; Rong Fan; Jin Chen; Tao Huang; Yanhong Wang; Jeremy Duncan; Ling Zhang; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2020)

Eukaryotic translation initiation factor 3 subunit b is a novel oncogenic factor in prostate cancer - Ping Xiang; Youwen Sun; Zhiqing Fang; Keqiang Yan; Yidong Fan (Mammalian Genome, 2020)

Discussion on position of China’s north-south transitional zone by comparative analysis of mountain altitudinal belts - Zhi-xiang Kou; Yong-hui Yao; Yu-fan Hu; Bai-ping Zhang (Journal of Mountain Science, 2020)

Scientific and technological power and international cooperation in the field of natural hazards: a bibliometric analysis - Jing-Li Fan; Shuo Shen; Jian-Da Wang; Shi-Jie Wei; Xian Zhang; Ping Zhong; Hang Wang (Natural Hazards, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Tracking fluid sources for skarn formation using scapolite geochemistry: an example from the Jinshandian iron skarn deposit, Eastern China - Li-Ping Zeng; Xin-Fu Zhao; Johannes Hammerli; Tian-Wei-Teng Fan; Carl Spandler (Mineralium Deposita, 2020)

Reverse time migration imaging of tunnels via the finite element method using an unstructured mesh - Jing Wang; Jiang-Ping Liu; Fei Cheng; Huai-Jie Yang; Yi-Fan Huang (Applied Geophysics, 2020)

Impedimetric biosensor fabricated with affinity peptides for sensitive detection of Escherichia coli O157:H7 - Fan Shi; Lingfeng Gan; Yibing Wang; Ping Wang (Biotechnology Letters, 2020)

Characterization of brain microstructural abnormalities in cirrhotic patients without overt hepatic encephalopathy using diffusion kurtosis imaging - Qing Sun; Wenliang Fan; Yuan Liu; Yan Zou; Natalie Wiseman; Zhifeng Kou; Ping Han (Brain Imaging and Behavior, 2020)
Cirrhosis is a major public health concern. However, little is known about the neurobiological mechanisms underlying brain microstructure alterations in cirrhotic patients. The purpose of this prospective study was to investigate brain microstructural alterations in cirrhosis with or without minimal hepatic encephalopathy (MHE) and their relationship with patients’ neurocognitive performance and disease duration using voxel-based analysis of diffusion kurtosis imaging (DKI). DKI data were acquired from 30 cirrhotic patients with MHE, 31 patients without MHE (NMHE) and 59 healthy controls. All DKI-derived parametric maps were compared across the three groups to investigate their group differences. Correlation analyses were further performed to assess relationships between altered imaging parameters and clinical data. Voxel-based analysis of DKI data results showed that MHE/NMHE patients had increased radial diffusivity, axial diffusivity (AD) and mean diffusivity in addition to decreased axial kurtosis (AK) and fractional anisotropy of kurtosis in several regions. Compared to controls, these regions were primarily the cingulum, temporal and frontal cortices. The DKI metrics (i.e., AK and AD) were correlated with clinical variables in the two patient groups. In conclusion, DKI is useful for detecting brain microstructural abnormalities in MHE and NMHE patients. Abnormal DKI parameters suggest alterations in brain microstructural complexity in cirrhotic patients, which may contribute to the neurobiological basis of neurocognitive impairment. These results may provide additional information on the pathophysiology of cirrhosis.

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

A new 3D JRC calculation method of rock joint based on laboratory-scale morphology testing and its application in shear strength analysis - Wenchen Fan; Ping Cao (Bulletin of Engineering Geology and the Environment, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

New anthraquinone and eurotinone analogue from the seeds of Senna obtusifolia and their inhibitory effects on human organic anion transporters 1 and 3 - Xu Pang; Li-Ming Wang; You-Cai Zhang; Li-Ping Kang; He-Shui Yu; Guan-Wei Fan; Li-Feng Han (Natural Product Research, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

On the rapid intensification for Typhoon Meranti (2016): convection, warm core, and heating budget - Xiba Tang; Fan Ping; Shuai Yang; Mengxia Li; Jing Peng (Frontiers of Earth Science, 2019)

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

Ablation of serum response factor in hepatic stellate cells attenuates liver fibrosis - Ming Kong; Wenxuan Hong; Yang Shao; Fangqiao Lv; Zhiwen Fan; Ping Li; Yong Xu; Junli Guo (Journal of Molecular Medicine, 2019)

Two new 5,6-epoxysterols from calcareous marine sponge Leucetta chagosensis - Wei-Zhuo Tang; Zhong-Zhen Yang; Fan Sun; Shu-Ping Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin (Natural Product Research, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

N2O production in the organic and mineral horizons of soil had different responses to increasing temperature - Lifei Sun; Changpeng Sang; Chao Wang; Zhenzhen Fan; Bo Peng; Ping Jiang; Zongwei Xia (Journal of Soils and Sediments, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Optimization of a 2A self-cleaving peptide-based multigene expression system for efficient expression of upstream and downstream genes in silkworm - Yuancheng Wang; Feng Wang; Sheng Xu; Riyuan Wang; Wenjing Chen; Kai Hou; Chi Tian; Fan Wang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2019)

Characteristic parameters of positive cloud-to-ground lightning channel - Ping Yuan; Rongrong Chen; Yanling Su; Bin Fan; Xuejuan Wang (Journal of Earth System Science, 2019)

Finite element reverse time migration imaging in tunnels using an unstructured mesh - Jing Wang; Jiang-Ping Liu; Fei Cheng; Huai-Jie Yang; Yi-Fan Huang (Applied Geophysics, 2019)

Endophytic fungi from the branches of Camellia taliensis (W. W. Smith) Melchior, a widely distributed wild tea plant - Xiaoxue Chen; Xulu Luo; Miaomiao Fan; Weilin Zeng; Chongren Yang; Jianrong Wu; Changlin Zhao; Yingjun Zhang; Ping Zhao (World Journal of Microbiology and Biotechnology, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Experimental and Numerical Study on the Damage Evolution of Random Rock Joint Surface During Direct Shear Under CNL Condition - Wenchen Fan; Ping Cao; Guodong Tang (Geotechnical and Geological Engineering, 2019)

Case study: using the point load test to estimate rock strength of tunnels constructed by a tunnel boring machine - Quan-Sheng Liu; Yi-Fan Zhao; Xiao-Ping Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Particle size distribution effects on deformation properties of graded aggregate base under cyclic loading - Hang Lin; Hu Wang; Xiang Fan; Ping Cao; Kefeng Zhou (European Journal of Environmental and Civil Engineering, 2019)

Dynamics of maize straw residue 13C incorporation into aggregates of a Mollisol as affected by long-term fertilization - Ming Li; Yang Wang; Fan Ding; Yingde Xu; Ping Zhu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

A multi-risk assessment framework for agricultural land use optimization - Haojie Cui; Ping Guo; Mo Li; Shanshan Guo; Fan Zhang (Stochastic Environmental Research and Risk Assessment, 2019)

Non-invasive Vagus Nerve Stimulation Protects Against Cerebral Ischemia/Reperfusion Injury and Promotes Microglial M2 Polarization Via Interleukin-17A Inhibition - Xiao-Ping Zhao; Yuan Zhao; Xiao-Ya Qin; Li-Yuan Wan; Xiao-Xuan Fan (Journal of Molecular Neuroscience, 2019)

HERV-W env regulates calcium influx via activating TRPC3 channel together with depressing DISC1 in human neuroblastoma cells - Yatang Chen; Qiujin Yan; Ping Zhou; Shan Li; Fan Zhu (Journal of NeuroVirology, 2019)

An inexact irrigation water allocation optimization model under future climate change - Youzhi Wang; Liu Liu; Ping Guo; Chenglong Zhang; Fan Zhang; Shanshan Guo (Stochastic Environmental Research and Risk Assessment, 2019)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

Origin and genetic family of Huhehu oil in the Hailar Basin, northeast China - Yao-Ping Wang; Fan Zhang; Yan-Rong Zou; Zhao-Wen Zhan; Yulan Cai (Acta Geochimica, 2018)

Dispersant-modified iron nanoparticles for mobility enhancement and TCE degradation: a comparison study - Yen-Ping Peng; Ting-Yu Chen; Chun-Yi Wu; Yu-Chen Chang; Ku-Fan Chen (Environmental Science and Pollution Research, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

DEM generation using Ziyuan-3 mapping satellite imagery without ground control points - Ping Zhou; Xinming Tang; Li Guo; Xia Wang; Wenfeng Fan (International Journal of Remote Sensing, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Assessing the genetic diversity of the critically endangered Chinese sturgeon Acipenser sinensis using mitochondrial markers and genome-wide single-nucleotide polymorphisms from RAD-seq - Jian Liu; Xinxin You; Pao Xu; Ping Zhuang; Yueping Zheng; Kai Zhang; Min Wang; Yunyun Lv; Gangchun Xu; Feng Zhao; Jianhui Wu; Houyong Fan; et al. (Science China Life Sciences, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Development characteristics of cloud-to-ground lightning with multiple grounding points - Bin Fan; Ping Yuan; Xuejuan Wang; Yang Zhao; Jianyong Cen; Yanling Su (Science China Earth Sciences, 2018)

Protective Effect of Moderate Exogenous Electric Field Stimulation on Activating Netrin-1/DCC Expression Against Mechanical Stretch-Induced Injury in Spinal Cord Neurons - Meili Liu; Chuanwei Yin; Zhengtai Jia; Kun Li; Zhifa Zhang; Yuchen Zhao; Xianghui Gong; Xiaoyu Liu; Ping Li; Yubo Fan (Neurotoxicity Research, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Responses of terrestrial nitrogen pools and dynamics to different patterns of freeze‐thaw cycle: A meta‐analysis - Decai Gao; Lei Zhang; Jun Liu; Bo Peng; Zhenzhen Fan; Weiwei Dai; Ping Jiang; Edith Bai (Global Change Biology, 2018)
Altered freeze‐thaw cycle ( FTC ) patterns due to global climate change may affect nitrogen (N) cycling in terrestrial ecosystems. However, the general responses of soil N pools and fluxes to different FTC patterns are still poorly understood. Here, we compiled data of 1519 observations from 63 studies and conducted a meta‐analysis of the responses of 17 variables involved in terrestrial N pools and fluxes to FTC . Results showed that under FTC treatment, soil NH 4 + , NO 3 − , NO 3 − leaching, and N 2 O emission significantly increased by 18.5%, 18.3%, 66.9%, and 144.9%, respectively; and soil total N ( TN ) and microbial biomass N ( MBN ) significantly decreased by 26.2% and 4.7%, respectively; while net N mineralization or nitrification rates did not change. Temperate and cropland ecosystems with relatively high soil nutrient contents were more responsive to FTC than alpine and arctic tundra ecosystems with rapid microbial acclimation. Therefore, altered FTC patterns (such as increased duration of FTC , temperature of freeze, amplitude of freeze, and frequency of FTC ) due to global climate warming would enhance the release of inorganic N and the losses of N via leaching and N 2 O emissions. Results of this meta‐analysis help better understand the responses of N cycling to FTC and the relationships between FTC patterns and N pools and N fluxes.

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

The V-ATPase subunit A is essential for salt tolerance through participating in vacuolar Na+ compartmentalization in Salicornia europaea - Sulian Lv; Ping Jiang; Fang Tai; Duoliya Wang; Juanjuan Feng; Pengxiang Fan; Hexigeduleng Bao; Yinxin Li (Planta, 2017)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Protective effect of dihydropteridine reductase against oxidative stress is abolished with A278C mutation - Yan-ting Gu; Yan-chun Wang; Hao-jun Zhang; Ting-ting Zhao; Si-fan Sun; Hua Wang; Bin Zhu; Ping Li (Journal of Zhejiang University-SCIENCE B, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

Loss of Hippocampal Oligodendrocytes Contributes to the Deficit of Contextual Fear Learning in Adult Rats Experiencing Early Bisphenol A Exposure - Xiao-Bin Xu; Shi-Jun Fan; Ye He; Xin Ke; Chen Song; Yao Xiao; Wen-Hua Zhang; Jun-Yu Zhang; Xiao-Ping Yin; Nobumasa Kato; Bing-Xing Pan (Molecular Neurobiology, 2017)

A live gI/gE-deleted pseudorabies virus (PRV) protects weaned piglets against lethal variant PRV challenge - Yue Yin; Zhiwen Xu; Xiaowan Liu; Ping Li; Fan Yang; Jun Zhao; Yi Fan; Xiangang Sun; Ling Zhu (Virus Genes, 2017)

Occurrence and genetic diversity analysis of apple stem pitting virus isolated from apples in China - Guo-Jun Hu; Ya-Feng Dong; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Zhengnan Li (Archives of Virology, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

Spontaneous Remission of Subcutaneous Scedosporiosis Caused by Scedosporium dehoogii in a Psoriatic Patient - Fang-Gu Li; Yan-Ping Yang; Wei Li; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2017)

Saline fluid interaction experiment in clastic reservoir of lacustrine basin - Fan Zhao; Wenyuan He; Chenggang Huang; Lirong Wu; Ping Zhang; Aiping Wang (Carbonates and Evaporites, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Transcriptome analysis in leaves of rice (Oryza sativa) under high manganese stress - Ping Li; Alin Song; Zhaojun Li; Fenliang Fan; Yongchao Liang (Biologia, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Tea polyphenols dominate the short-term tea (Camellia sinensis) leaf litter decomposition - Dong-mei Fan; Kai Fan; Cui-ping Yu; Ya-ting Lu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Frequency of germline PALB2 mutations among women with epithelial ovarian cancer - Joanne Kotsopoulos; Victoria Sopik; Barry Rosen; Isabel Fan; John R. McLaughlin; Harvey Risch; Ping Sun; Steven A. Narod; Mohammad R. Akbari (Familial Cancer, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Transcriptome profiling indicating canine parvovirus type 2a as a potential immune activator - Xu-Xu Fan; Yuan Gao; Long Shu; Yan-Quan Wei; Xue-Ping Yao; Sui-Zhong Cao; Guang-Neng Peng; Xiang-Tao Liu; Shi-Qi Sun (Virus Genes, 2016)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Integrated transcriptome analysis of human iPS cells derived from a fragile X syndrome patient during neuronal differentiation - Ping Lu; Xiaolong Chen; Yun Feng; Qiao Zeng; Cizhong Jiang; Xianmin Zhu; Guoping Fan; Zhigang Xue (Science China Life Sciences, 2016)

An Experimental and Numerical Study on Mechanical Behavior of Ubiquitous-Joint Brittle Rock-Like Specimens Under Uniaxial Compression - Ri-hong Cao; Ping Cao; Xiang Fan; Xinguang Xiong; Hang Lin (Rock Mechanics and Rock Engineering, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Geochemistry of Altungol cap dolostones from the Tarim Basin, NW China - Fan Feng; Ping Guan; Wenhui Liu; Wei Zhang; Peixian Liu; Xing Jian; Ling Fu (Arabian Journal of Geosciences, 2016)

Zinc Attenuates Tubulointerstitial Fibrosis in Diabetic Nephropathy Via Inhibition of HIF Through PI-3K Signaling - Xiuli Zhang; Dan Liang; Jingyue Fan; Xu Lian; Yue Zhao; Xuemei Wang; Zhi-Hong Chi; Ping Zhang (Biological Trace Element Research, 2016)

Experimental Investigation of the Mechanical Behavior of Bedded Rocks and Its Implication for High Sidewall Caverns - Yang-Yi Zhou; Xia-Ting Feng; Ding-Ping Xu; Qi-Xiang Fan (Rock Mechanics and Rock Engineering, 2016)

Microbial acclimation triggered loss of soil carbon fractions in subtropical wetlands subjected to experimental warming in a laboratory study - Hang Wang; HongYi Li; Fan Ping; ChunLei Yue; ZhiJian Zhang (Plant and Soil, 2016)

Acid fluids reconstruction clastic reservoir experiment in Qaidam saline lacustrine Basin, China - Chenggang Huang; Fan Zhao; Jianying Yuan; Ping Sun; Shiming Zhang (Carbonates and Evaporites, 2016)

Kerion and Tinea Corporis Caused by Rabbit-Derived Trichophyton interdigitale in Three Siblings and One Consulting Doctor Using β-Tubulin Gene to Identify the Pathogen - Yan-Ping Yang; Ping Sheng; Zhong Liu; Wen Li; Jie-Di Wang; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

A New Methodology for Open Pit Slope Design in Karst-Prone Ground Conditions Based on Integrated Stochastic-Limit Equilibrium Analysis - Ke Zhang; Ping Cao; Guowei Ma; Wenchen Fan; Jingjing Meng; Kaihui Li (Rock Mechanics and Rock Engineering, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Association of the C2–CFB locus with non-infectious uveitis, specifically predisposed to Vogt–Koyanagi–Harada disease - Mingming Yang; Jiao-jie Fan; Jun Wang; Yan Zhao; Yan Teng; Ping Liu (Immunologic Research, 2016)

A review of neurotoxicity of microcystins - Yufei Hu; Jun Chen; Huihui Fan; Ping Xie; Jun He (Environmental Science and Pollution Research, 2016)

Erratum to: Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2016)

PPM1D exerts its oncogenic properties in human pancreatic cancer through multiple mechanisms - Bo Wu; Bo-Min Guo; Jie Kang; Xian-Zhao Deng; You-Ben Fan; Xiao-Ping Zhang; Kai-Xing Ai (Apoptosis, 2016)

bmo-miR-0001 and bmo-miR-0015 down-regulate expression of Bombyx mori fibroin light chain gene in vitro - Chen Chen; Yang-yang Fan; Xin Wang; Fei Song; Tao Jiang; Ping Qian; Shun-ming Tang; Xing-jia Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

FBXW7-Induced MTOR Degradation Forces Autophagy to Counteract Persistent Prion Infection - Yin Xu; Chan Tian; Jing Sun; Jin Zhang; Ke Ren; Xue-Yu Fan; Ke Wang; Hui Wang; Yu-E Yan; Cao Chen; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Silicon ameliorates manganese toxicity by regulating both physiological processes and expression of genes associated with photosynthesis in rice (Oryza sativa L.) - Ping Li; Alin Song; Zhaojun Li; Fenliang Fan; Yongchao Liang (Plant and Soil, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2015)

Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; James A. Cotton; Joe D. Parker; Gábor Csorba; Burton K. Lim; Judith L. Eger; Chia‐Hong Chen; Cheng‐Han Chou; Stephen J. Rossiter (Molecular Ecology, 2015)
Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. Mt DNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi , to the exclusion of M. gracilis . To dissect the basis of these conflicts between nc DNA and mt DNA , we analysed sequences from 10 anonymous nc DNA loci with * beast and isolation‐with‐migration and found two distinct clades of M. eleryi , one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.

Detection and genetic variation analysis of grapevine fanleaf virus (GFLV) isolates in China - Jun Zhou; Xudong Fan; Yafeng Dong; Zun ping Zhang; Fang Ren; Guojun Hu (Archives of Virology, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Molecular characterizations of two grapevine rupestris stem pitting-associated virus isolates from China - Guo-Jun Hu; Ya-Feng Dong; Hong-Juan Zhu; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Jun Zhou (Archives of Virology, 2015)

TIPE2 acts as a negative regulator linking NOD2 and inflammatory responses in myocardial ischemia/reperfusion injury - Hongyu Zhang; Tianfeng Zhu; Wenwen Liu; Xin Qu; Ye Chen; Ping Ren; Ziying Wang; Xinbing Wei; Yan Zhang; Fan Yi (Journal of Molecular Medicine, 2015)

A newly isolated Haloalkaliphilic bacterium from middle–late Eocene halite formed in salt lakes in China - Fan-Wei Meng; Xiu-Qiang Wang; Pei Ni; Gunther Kletetschka; Chun-He Yang; Yin-Ping Li; Yong-Hua Yang (Carbonates and Evaporites, 2015)

Cutaneous Chromoblastomycosis Caused by Veronaea botryosa in a Patient with Pemphigus Vulgaris and Review of Published Reports - Cheng-Yao Zhu; Yan-Ping Yang; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Binary chromatographic fingerprint analysis of Stemonae Radix from three Stemona plants and its applications - Lan-Lan Fan; Feng Xu; Jun-Ping Hu; Dong-Hui Yang; Hu-Biao Chen; Katsuko Komatsu; Shu Zhu; Ming-Ying Shang; Xuan Wang; Shao-Qing Cai (Journal of Natural Medicines, 2015)

Genetic diversity and recombination analysis of grapevine leafroll-associated virus 1 from China - Xudong Fan; Ni Hong; Yafeng Dong; Yanxia Ma; Zun Ping Zhang; Fang Ren; Guojun Hu; Jun Zhou; Guoping Wang (Archives of Virology, 2015)

Regional specific adaptation of the endothelial glycocalyx dimension in tail-suspended rats - Hongyan Kang; Lianwen Sun; Yunfei Huang; Zhenze Wang; Ping Zhao; Yubo Fan; Xiaoyan Deng (Pflügers Archiv - European Journal of Physiology, 2015)

Modeling the Progressive Failure of Jointed Rock Slope Using Fracture Mechanics and the Strength Reduction Method - Ke Zhang; Ping Cao; Jingjing Meng; Kaihui Li; Wenchen Fan (Rock Mechanics and Rock Engineering, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Development and characterization of polymorphic microsatellite loci in Ficus altissima - Yi-Ping Ma; Yi-Fan Kong; Yawen Cao; Yi-Su Shi (Conservation Genetics Resources, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

HES1 promotes metastasis and predicts poor survival in patients with colorectal cancer - Ruixue Yuan; Jia Ke; Lei Sun; Zhen He; Yifeng Zou; Xiaosheng He; Yufeng Chen; Xianrui Wu; Zerong Cai; Lei Wang; Jianping Wang; Xinjuan Fan; et al. (Clinical & Experimental Metastasis, 2015)

Effects of desipramine treatment on stress-induced up-regulation of norepinephrine transporter expression in rat brains - Yan Fan; Ping Chen; Ying Li; Gregory A. Ordway; Meng-Yang Zhu (Psychopharmacology, 2015)

l-Ornithine Schiff base–copper and –cadmium complexes as new proteasome inhibitors and apoptosis inducers in human cancer cells - Zhongyu Zhang; Caifeng Bi; Yuhua Fan; Nan Zhang; Rahul Deshmukh; Xingchen Yan; Xiuwen Lv; Pengfei Zhang; Xia Zhang; Q. Ping Dou (JBIC Journal of Biological Inorganic Chemistry, 2015)

Rapid development of proteomics in China: from the perspective of the Human Liver Proteome Project and technology development - Ning Li; ZhongWei Xu; LinHui Zhai; YanChang Li; FengXu Fan; JunJie Zheng; Ping Xu; FuChu He (Science China Life Sciences, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Phylogenetic diversity and conservation of protected click beetles (Campsosternus spp.) in Taiwan: a molecular approach to clarifying species status - Jui-Fan Hsieh; Ming-Luen Jeng; Chia-Hung Hsieh; Chiun-Cheng Ko; Ping-Shih Yang (Journal of Insect Conservation, 2014)

Observation of the middle intestinal tight junction structure, cloning and studying tissue distribution of the four Claudin genes of the grass carp (Ctenopharyngodon idellus) - Fan Xu; Yuan-Tu Ye; Chun-Fang Cai; Ping Wu; Lin Song; Meng Liu; Lin-Jie Yao; Jiao-Jiao Dong; Yu-Wei Huang; Zhi Gong; Jie Qin; Liang Song (Fish Physiology and Biochemistry, 2014)

MicroRNA-2 Suppresses Lewis Lung Cancer Cells Proliferation, Invasion, and Migration in Tumor-Bearing Mice - Xu Wang; Ping-fan Wang; Wu-ying Yuan (Cell Biochemistry and Biophysics, 2014)

Mitochondrial genomes of domestic animals need scrutiny - Ni‐Ni Shi; Long Fan; Yong‐Gang Yao; Min‐Sheng Peng; Ya‐Ping Zhang (Molecular Ecology, 2014)
More than 1000 complete or near‐complete mitochondrial DNA (mt DNA ) sequences have been deposited in GenBank for eight common domestic animals (cattle, dog, goat, horse, pig, sheep, yak and chicken) and their close wild ancestors or relatives, as well. Nevertheless, few efforts have been performed to evaluate the sequence data quality. Herein, we conducted a phylogenetic survey of these complete or near‐complete mt DNA sequences based on mt DNA haplogroup trees for the eight animals. We show that errors due to artificial recombination, surplus of mutations and phantom mutations do exist in 14.5% (194/1342) of mt DNA sequences and all of them should be treated with wide caution. We propose some caveats for future mt DNA studies of domestic animals.

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Urokinase-type plasminogen activator receptor regulates apoptotic sensitivity of colon cancer HCT116 cell line to TRAIL via JNK-p53 pathway - Xiufeng Liu; Fan Qiu; Zhipeng Liu; Yan Lan; Kai Wang; Ping-Kun Zhou; Yao Wang; Zi-Chun Hua (Apoptosis, 2014)

A novel variant in TBX20 (p.D176N) identified by whole-exome sequencing in combination with a congenital heart disease related gene filter is associated with familial atrial septal defect - Ji-jia Liu; Liang-liang Fan; Jin-lan Chen; Zhi-ping Tan; Yi-feng Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Promoters of HcTPS1 and HcTPS2 Genes from Hedychium coronarium Direct Floral-Specific, Developmental-Regulated and Stress-Inducible Gene Expression in Transgenic Tobacco - Xin-Yue Li; Shao-Yuan Zheng; Rang-Cai Yu; Yan-Ping Fan (Plant Molecular Biology Reporter, 2014)

Identification and characterization of six cytochrome P450 genes belonging to CYP4 and CYP6 gene families in the silkworm, Bombyx mori - Bing Li; Hua Zhang; Min Ni; Bin-bin Wang; Fan-chi Li; Kai-zhun Xu; Wei-de Shen; Qing-you Xia; Ping Zhao (Molecular Biology Reports, 2014)

Urinary metabolites of di(2-ethylhexyl) phthalate relation to sperm motility, reactive oxygen species generation, and apoptosis in polyvinyl chloride workers - Li-Ping Huang; Ching-Chang Lee; Jer-Pei Fan; Po-Hsiu Kuo; Tung-Sheng Shih; Ping-Chi Hsu (International Archives of Occupational and Environmental Health, 2014)

A comparative study of the atmospheric circulations associated with rainy-season floods between the Yangtze and Huaihe River Basins - Fan Ping; XiBa Tang; ShouTing Gao; ZheXian Luo (Science China Earth Sciences, 2014)

Influence of casein phosphopeptide-amorphous calcium phosphate application, smear layer removal, and storage time on resin-dentin bonding - Jun Lin; Wei-ying Zheng; Peng-ruo-feng Liu; Ning Zhang; Hui-ping Lin; Yi-jing Fan; Xin-hua Gu; Oliver Vollrath; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2014)

Comparative rangewide phylogeography of four endemic T aiwanese bat species - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; Jon Flanders; Stephen J. Rossiter (Molecular Ecology, 2014)
Phylogeographic reconstructions of codistributed taxa can help reveal the interplay between abiotic factors, such as altitude and climate, and species‐specific attributes, in shaping patterns of population genetic structure. Recent studies also demonstrate the value of both rangewide sampling and species distribution modelling ( SDM ) in comparative phylogeography. Here, we combine these approaches to study the population histories of four phylogenetically related forest‐dependent bat species. All are endemic to the mountainous island of Taiwan but show differences in their tolerance to altitude, with M urina gracilis considered to be a high‐altitude specialist, M. recondita and K erivoula sp. low‐altitude specialists, and M . puta an altitudinal generalist. We tested the prediction that contrasting habitat preferences would impact on patterns of past and contemporary gene flow and found broad concordance between the results of population genetic analyses and species distribution models based on the Model for Interdisciplinary Research on Climate. Both lowland species showed evidence of genetic divergence between the east and west of the island, consistent with SDM s that indicated the Central Mountain Range ( CMR ) has presented a long‐term and continuous barrier to gene flow since before the Last Glacial Maximum. In contrast, M urina gracilis and M. puta showed lower degrees of historical isolation and genetic differentiation associated with the CMR , reflecting greater gene flow, possibly coupled with past population growth in M . puta . Together our results highlight the usefulness of combining distribution models with phylogeographic analyses to understand the drivers of genetic structure.

Hopping out of Mindanao: Miocene‐Pliocene geological processes and cross‐island dispersal as major drivers of diversity for Philippine treehoppers - Yong‐Chao Su; Jo‐Fan Wang; Reagan Joseph T. Villanueva; Olga M. Nuñeza; Chung‐Ping Lin (Journal of Biogeography, 2014)
Aim We investigated the biogeographical history of an endemic Philippine treehopper, Pyrgonota bifoliata (Membracidae), to test the effect of Neogene geological events and Pleistocene climate change in generating speciation within the Philippines. Location The Philippine archipelago. Methods Phylogenies were reconstructed based on the mitochondrial cytochrome c oxidase I subunit ( cox1 ) and nuclear wingless ( wg ) genes using maximum parsimony, maximum likelihood and Bayesian criteria. Divergence times were estimated in beast based on a range of mutation rates. Ancestral ranges were reconstructed using rasp (Reconstruct Ancestral State in Phylogenies) and Bayesian stochastic search variable selection (BSSVS). Species boundaries were tested using the Bayesian general mixed Yule coalescent ( bGMYC ) and Bayesian phylogenetic and phylogeography (BPP) methods. Results Pyrgonota bifoliata showed one of the lowest levels of between‐Pleistocene island genetic variation among all the taxa examined. Most Pleistocene aggregate island complex ( PAIC ) lineages and extant P. bifoliata originated before the onset of the first extensive Pleistocene glacial cycle. Ancestral P. bifoliata originated in the late Miocene from Mindanao, followed by a sequential northwards colonization of the Visayan Islands and Luzon in the Pliocene–early Pleistocene, which coincided with the spatial reorganization of the Philippines. The statistically delimited nine provisional species of what we now view as the P. bifoliata species complex correspond to current island boundaries and specialized host plants. Main conclusions The temporally calibrated phylogeny of P. bifoliata represents the first invertebrate study to support the hypothesis that Miocene–Pliocene geological events and consequent cross‐island dispersal were pivotal promoters of species diversity in the Philippines. We hypothesize that ecological adaptation to specialized host plants, together with either local selection or genetic drift through within‐island allopatric isolation, present a plausible in situ speciation mechanism for the origin of these herbivorous insects.

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

The suitability of Ostrinia furnacalis (Lepidoptera: Crambidae) eggs for Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) can be changed by T. ostriniae - Ping Zhu; Yan-Feng Zhang; Qiong-Ting Song; Fan Zhang; Yuan-Xi Li (Applied Entomology and Zoology, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Biological and genomic analysis of a PBSX-like defective phage induced from Bacillus pumilus AB94180 - Tingting Jin; Xiaoming Zhang; Yang Zhang; Zhongsheng Hu; Zhengwei Fu; Junpeng Fan; Ming Wu; Yi Wang; Ping Shen; Xiangdong Chen (Archives of Virology, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Involvement of α7 nAChR Signaling Cascade in Epigallocatechin Gallate Suppression of β-Amyloid-Induced Apoptotic Cortical Neuronal Insults - Xijing Zhang; Mingmei Wu; Fan Lu; Na Luo; Zu-Ping He; Hao Yang (Molecular Neurobiology, 2014)

A simulation of the merger of convective clouds in the torrential rainfalls associated with the Meiyu front - Fan Ping; Zhexian Luo; Xiba Tang; Liang Hu (Meteorology and Atmospheric Physics, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase - Ping-Lin Ong; Tzu-Ting Chuang; Tzu-Fan Wang; Long-Liu Lin (Biologia, 2014)

Shh signaling, negatively regulated by BMP signaling, inhibits the osteo/dentinogenic differentiation potentials of mesenchymal stem cells from apical papilla - Qingsong Jiang; Juan Du; Xiaonan Yin; Zhaochen Shan; Yushi Ma; Ping Ma; Juan Du; Zhipeng Fan (Molecular and Cellular Biochemistry, 2013)

Isolation and identification of a new ent -kaurane diterpenoid from the leaves of Isodon japonica - Wei Liu; Bing-Lin Fan; Hong-Yun Guo; Yong-Liang Yuan; Hui-Juan Liang; Su-Ping Bai (Natural Product Research, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Depletion of histone demethylase KDM2A inhibited cell proliferation of stem cells from apical papilla by de-repression of p15INK4B and p27Kip1 - Runtao Gao; Rui Dong; Juan Du; Ping Ma; Songlin Wang; Zhipeng Fan (Molecular and Cellular Biochemistry, 2013)

Diversity arrays technology (DArT) for studying the genetic polymorphism of flue-cured tobacco (Nicotiana tabacum) - Xiu-ping Lu; Bing-guang Xiao; Yong-ping Li; Yi-jie Gui; Yu Wang; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2013)

Display of Human Proinsulin on the Bacillus subtilis Spore Surface for Oral Administration - Fan Feng; Ping Hu; Liang Chen; Qi Tang; Chaoqun Lian; Qin Yao; Keping Chen (Current Microbiology, 2013)

Screening for differentially methylated genes among human colorectal cancer tissues and normal mucosa by microarray chip - Wei Chen; Jun Xiang; De-Feng Chen; Bei-Bei Ni; Hao Chen; Xin-Juan Fan; Pu-Ning Wang; Shun-Xin Song; Le-Kun Fang; Huan-Yu Xiao; Lei Wang; Jian-Ping Wang (Molecular Biology Reports, 2013)

Distribution and accumulation characteristics of heavy metals in sediments in southern sea area of Huludao City, China - Yan Wang; Ruhai Liu; Dejiang Fan; Ping Yu; Jinyu Wang; Aikun Tang (Chinese Geographical Science, 2013)

Response of bedload transport, submarine topography, and dune internal structures to typhoon processes off Dongfang coast in the Beibu Gulf - Xiaochuan Ma; Jun Yan; Fengxin Fan; Ping Yao (Acta Oceanologica Sinica, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

Involvement of large conductance Ca2+-activated K+ channel in laminar shear stress-induced inhibition of vascular smooth muscle cell proliferation - Xiaoling Jia; Jingyun Yang; Wei Song; Ping Li; Xia Wang; Changdong Guan; Liu Yang; Yan Huang; Xianghui Gong; Meili Liu; Lisha Zheng; Yubo Fan (Pflügers Archiv - European Journal of Physiology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Molecular characterization of Japanese encephalitis viruses circulating in pigs and mosquitoes on pig farms in the Chinese province of Henan - Man Teng; Jun Luo; Jian-Ming Fan; Lu Chen; Xing-Tao Wang; Wu Yao; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2013)

Evaluation of landslide risk based on synchronization of nonlinear motions in observed data - Da-Chao Lin; Jing-Luo Cai; Zhang-Lin Guo; Fan-Lei Zeng; Feng-Ping An; Hai-Bo Liu (Natural Hazards, 2013)

Quantitative assessment of the association between miR-196a2 rs11614913 polymorphism and gastrointestinal cancer risk - Fang Wang; Guo-Ping Sun; Yan-Feng Zou; Lu-Lu Fan; Bing Song (Molecular Biology Reports, 2013)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

The genotypes of citrus tristeza virus isolates from China revealed by sequence analysis of multiple molecular markers - Guan-wei Wu; Song Pan; Guo-ping Wang; Min Tang; Yong Liu; Fan Yang; Ni Hong (Archives of Virology, 2013)

Involvement of antioxidant defense system in chill hardening-induced chilling tolerance in Jatropha curcas seedlings - Ping-Xing Ao; Zhong-Guang Li; Dong-Mei Fan; Ming Gong (Acta Physiologiae Plantarum, 2013)

1,10-Phenanthroline promotes copper complexes into tumor cells and induces apoptosis by inhibiting the proteasome activity - Zhen Zhang; Caifeng Bi; Sara M. Schmitt; Yuhua Fan; Lili Dong; Jian Zuo; Q. Ping Dou (JBIC Journal of Biological Inorganic Chemistry, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Relationships Between Femoral Strength Evaluated by Nonlinear Finite Element Analysis and BMD, Material Distribution and Geometric Morphology - He Gong; Ming Zhang; Yubo Fan; Wai Leung Kwok; Ping Chung Leung (Annals of Biomedical Engineering, 2012)

Association of the microRNA-499 variants with susceptibility to hepatocellular carcinoma in a Chinese population - Yu Xiang; Song Fan; Ju Cao; Shifeng Huang; Li-ping Zhang (Molecular Biology Reports, 2012)

Improving the acidic stability of a methyl parathion hydrolase by changing basic residues to acidic residues - Lu Huang; Ping Wang; Jian Tian; Huachen Jiang; Ningfeng Wu; Peilong Yang; Bin Yao; Yunliu Fan (Biotechnology Letters, 2012)

A first set of polymorphic microsatellite loci isolated from Rhinogobio cylindricus - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen; Shao Ping Liu; Fan Rrong Zhang; Dong Yang; Lai Ning Yu (Conservation Genetics Resources, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Analysis of reconstructed annual precipitation from tree-rings for the past 500 years in the middle Qilian Mountain - QinHua Tian; XiuJi Zhou; XiaoHua Gou; Ping Zhao; ZeXin Fan; Samuli Helama (Science China Earth Sciences, 2012)

Silicon ameliorates manganese toxicity by regulating manganese transport and antioxidant reactions in rice (Oryza sativa L.) - Ping Li; Alin Song; Zhaojun Li; Fenliang Fan; Yongchao Liang (Plant and Soil, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Simulations of the motion of tropical cyclone-like vortices in the presence of synoptic and mesoscale circulations - Zhexian Luo; Fan Ping (Advances in Atmospheric Sciences, 2012)

Mechanism for initial brows-like meso-scale vortex effects on tropical cyclone track - ZheXian Luo; Fan Ping (Science China Earth Sciences, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Missense substitutions in the GAS1 protein present in holoprosencephaly patients reduce the affinity for its ligand, SHH - Daniel E. Pineda-Alvarez; Erich Roessler; Ping Hu; Kshitij Srivastava; Benjamin D. Solomon; C. Evan Siple; Chen-Ming Fan; Maximilian Muenke (Human Genetics, 2012)

Adaptive characteristics of grassland community structure and leaf traits along an altitudinal gradient on a subtropical mountain in Chongqing, China - Lu-lu Song; Jiang-wen Fan; Warwick Harris; Shao-hong Wu; Hua-ping Zhong; Yong-chun Zhou; Ning Wang; Xu-dong Zhu (Plant Ecology, 2012)

Experimental Pathogenicity of a Clinical Isolate of Trichosporon dermatis in a Murine Model - Ying-Ping Lin; Yan-Ping Yang; Wen-Ming Huang; Yong-Hua Chen; Shun-Fan Li; Yi-Ming Fan (Mycopathologia, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

Association of BLK (rs13277113, rs2248932) polymorphism with systemic lupus erythematosus: a meta-analysis - Ye Fan; Jin-Hui Tao; Li-Ping Zhang; Lian-Hong Li; Dong-Qing Ye (Molecular Biology Reports, 2011)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

Polyethylenimine-cyclodextrin-tegafur conjugate shows anti-cancer activity and a potential for gene delivery - Qi-da Hu; Hui Fan; Wei-jian Lou; Qing-qing Wang; Gu-ping Tang (Journal of Zhejiang University-SCIENCE B, 2011)

The effects of simvastatin on angiogenesis: studied by an original model of atherosclerosis and acute myocardial infarction in rabbit - Wei Shen; Hai-Ming Shi; Wei-Hu Fan; Xin-Ping Luo; Bo Jin; Yong Li (Molecular Biology Reports, 2011)

The alleviation of zinc toxicity by silicon is related to zinc transport and antioxidative reactions in rice - Alin Song; Ping Li; Zhaojun Li; Fenliang Fan; Miroslav Nikolic; Yongchao Liang (Plant and Soil, 2011)

Mammalian cell entry gene family of Mycobacterium tuberculosis - Fan Zhang; Jian-Ping Xie (Molecular and Cellular Biochemistry, 2011)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

The natural compound n-butylidenephthalide derived from the volatile oil of Radix Angelica sinensis inhibits angiogenesis in vitro and in vivo - Ju-Ching Yeh; Tereza Cindrova-Davies; Mirella Belleri; Lucia Morbidelli; Nigel Miller; Chin-Wen Chantal Cho; Kelvin Chan; Yi-Tao Wang; Guo-An Luo; Marina Ziche; Marco Presta; David Stephen Charnock-Jones; et al. (Angiogenesis, 2011)

Molecular cloning and analysis of the UDP-Glucose Pyrophosphorylase in Streptococcus equi subsp. zooepidemicus - Zhe Ma; Hong-jie Fan; Cheng-ping Lu (Molecular Biology Reports, 2011)

Regional dependence of microphysical and radiative effects of ice clouds on vertical structures of tropical tropospheric temperature - Fan Ping; Zhexian Luo; Xiaofan Li (Meteorology and Atmospheric Physics, 2011)

Antitumor Activity of a Combination of rAd2p53 Adenoviral Gene Therapy and Radiotherapy in Esophageal Carcinoma - Ping Lu; Xiaoyu Yang; Yanmei Huang; Zhihong Lu; Zhanhui Miao; Qiudong Liang; Yanli Zhu; Qingxia Fan (Cell Biochemistry and Biophysics, 2011)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)

Increasing of Blood-tumor Barrier Permeability through Paracellular Pathway by Low-frequency Ultrasound Irradiation In Vitro - Lilin Fan; Yunhui Liu; Haoqiang Ying; Yixue Xue; Zhen Zhang; Ping Wang; Libo Liu; Hua Zhang (Journal of Molecular Neuroscience, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Reproductive failure in wild boars associated to porcine parvovirus infection and in vivo and in vitro characterization of the causal isolate - Chao-fan Zhang; Cui-Ping Song; Chang-mu Chen; Shang-jin Cui; Lan-fei Miao (Tropical Animal Health and Production, 2010)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Investigation of fine and complex vortex circulation structures - ZheXian Luo; GeLan Ma; Fan Ping (Science China Earth Sciences, 2010)

Dextran Gadolinium Complexes as Contrast Agents for Magnetic Resonance Imaging to Sentinel Lymph Nodes - Guo-Ping Yan; Wei Xu; Lian Yang; Liang Li; Fan Liu; Qing-Zhong Guo (Pharmaceutical Research, 2010)

Molecular characterization of T-DNA integration sites in transgenic birch - Fan-Suo Zeng; Ya-Guang Zhan; Hong-Cui Zhao; Ying Xin; Feng-Hui Qi; Chuan-Ping Yang (Trees, 2010)

A possible role of myristoylated alanine-rich C kinase substrate in endocytic pathway of Alzheimer’s disease - Rui Su; Zhen-Yun Han; Ji-Ping Fan; Yun-Ling Zhang (Neuroscience Bulletin, 2010)

Effect of enalapril on plasma homocysteine levels in patients with essential hypertension - Fang-fang Fan; Yong Huo; Xu Wang; Xin Xu; Bin-yan Wang; Xi-ping Xu; Jian-ping Li (Journal of Zhejiang University-SCIENCE B, 2010)

Soil microbial properties under N and P additions in a semi-arid, sandy grassland - Lu-Jun Li; De-Hui Zeng; Zhan-Yuan Yu; Zhi-Ping Fan; Rong Mao (Biology and Fertility of Soils, 2010)

The relationship between invasive alien species and main climatic zones - Juan Shi; You-Qing Luo; Fan Zhou; Ping He (Biodiversity and Conservation, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Effects of Cadmium on Absorption, Excretion, and Distribution of Nickel in Rats - Zhan Li; Jun-Ying Gu; Xian-Wen Wang; Qiao-Hui Fan; Yan-Xia Geng; Zong-Xian Jiao; Yi-Ping Hou; Wang-Suo Wu (Biological Trace Element Research, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Comparative study on in vitro transformation of paralytic shellfish poisoning (PSP) toxins in different shellfish tissues - Hua Tian; Chunlei Gao; Zongling Wang; Ping Sun; Shiliang Fan; Mingyuan Zhu (Acta Oceanologica Sinica, 2010)

Epigallocatechin-3-gallate enhances ischemia/reperfusion-induced apoptosis in human umbilical vein endothelial cells via AKT and MAPK pathways - Tianpeng Zhang; Dan Yang; Yongna Fan; Ping Xie; Huihua Li (Apoptosis, 2009)

Could nested PCR be applicable for the study of microbial diversity? - Zhen-Yu Fan; Xiao-Ran Li; Dan-Ping Mao; Gen-Feng Zhu; Sheng-Yue Wang; Zhe-Xue Quan (World Journal of Microbiology and Biotechnology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

BREVIS RADIX is involved in cytokinin-mediated inhibition of lateral root initiation in Arabidopsis - Jing Li; Xiaorong Mo; Jirong Wang; Nannan Chen; Huan Fan; Chunyan Dai; Ping Wu (Planta, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2008)

Using a short-term parameter of heart rate variability to distinguish awake from isoflurane anesthetic states - Hui-Hsun Huang; Yi-Hui Lee; Hsiao-Lung Chan; Yong-Ping Wang; Chi-Hsiang Huang; Shou-Zen Fan (Medical & Biological Engineering & Computing, 2008)

Characterization of Citrus tristeza virus strains from southern China based on analysis of restriction patterns and sequences of their coat protein genes - Bo Jiang; Ni Hong; Guo-Ping Wang; John Hu; Jian-Kun Zhang; Cai-Xia Wang; Yong Liu; Xu-Dong Fan (Virus Genes, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Analysis of synonymous codon usage and evolution of begomoviruses - Xiao-zhong Xu; Qing-po Liu; Long-jiang Fan; Xiao-feng Cui; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2008)

Transgenic maize plants expressing a fungal phytase gene - Rumei Chen; Guangxing Xue; Ping Chen; Bin Yao; Wenzhu Yang; Qianli Ma; Yunliu Fan; Zuoyu Zhao; Mitchell C. Tarczynski; Jinrui Shi (Transgenic Research, 2008)

Involvement of GlnK, a PII protein, in control of nitrogen fixation and ammonia assimilation in Pseudomonas stutzeri A1501 - Sheng He; Ming Chen; Zhihong Xie; Yongliang Yan; Hongquan Li; Ying Fan; Shuzhen Ping; Min Lin; Claudine Elmerich (Archives of Microbiology, 2008)

DFL, a FLORICAULA/LEAFY homologue gene from Dendranthema lavandulifolium is expressed both in the vegetative and reproductive tissues - Yue-Ping Ma; Xiao-Hua Fang; Fan Chen; Si-Lan Dai (Plant Cell Reports, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Sensing Escherichia coli O157:H7 via frequency shift through a self-assembled monolayer based QCM immunosensor - Li-jiang Wang; Chun-sheng Wu; Zhao-ying Hu; Yuan-fan Zhang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2008)

11,20-Epoxybriaranes from the Gorgonian Coral Ellisella robusta (Ellisellidae) - Yu-Mine Su; Tung-Yung Fan; Ping-Jyun Sung (Natural Product Research, 2007)

The Improvement of Spinach Growth by Nano-anatase TiO2 Treatment Is Related to Nitrogen Photoreduction - Fan Yang; Chao Liu; Fengqing Gao; Mingyu Su; Xiao Wu; Lei Zheng; Fashui Hong; Ping Yang (Biological Trace Element Research, 2007)

Cloning and promoter activity of rat Smad1 5′-flanking region in rat hepatic stellate cells - Yu Sun; Jianghong Fan; Hong Shen; Ping Li; Peter Cattini; Yuewen Gong (Molecular and Cellular Biochemistry, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Optimization of an ethanol production medium in very high gravity fermentation - Fan-Qiang Wang; Cui-Juan Gao; Chun-Yu Yang; Ping Xu (Biotechnology Letters, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Detection and estrogen regulation of leptin receptor expression in rat dorsal root ganglion - Hong Ping Chen; Jingjing Fan; Sheng Cui (Histochemistry and Cell Biology, 2006)

Binding interactions of pefloxacin mesylate with bovine lactoferrin and human serum albumin - Ji-cai Fan; Xiang Chen; Yun Wang; Cheng-ping Fan; Zhi-cai Shang (Journal of Zhejiang University-SCIENCE B, 2006)

Expression of cysteine sulfinate decarboxylase (CSD) in male reproductive organs of mice - Jian Hua Li; Ya Qin Ling; Jing Jing Fan; Xiao Ping Zhang; Sheng Cui (Histochemistry and Cell Biology, 2006)

Purification and characterization of hatching enzyme from flounder Paralichthys olivaceus - Zhen-Ping Shi; Ting-Jun Fan; Ri-Shan Cong; Xiao-Feng Wang; Wen-Jie Sun; Ling-Ling Yang (Fish Physiology and Biochemistry, 2006)

Cloud microphysical processes associated with the diurnal variations of tropical convection: A 2D cloud resolving modeling study - Shouting Gao; Fan Ping; Xiaofan Li (Meteorology and Atmospheric Physics, 2006)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Phylogenetic Analysis of Eight Genes of H9N2 Subtype Influenza Virus: A Mainland China Strain Possessing Early Isolates’ Genes that have been Circulating - Jian-Hong Lu; Xiu-Fan Liu; Wei-Xing Shao; Yu-Liang Liu; Dong-Ping Wei; Hong-Qi Liu (Virus Genes, 2005)

Nitric oxide modulates hepatocyte growth factor/scatter factor-induced angiogenesis - Shiladitya Sengupta; Lynda A. Sellers; Ermanno Gherardi; Ram Sasisekharan; Tai-Ping D. Fan (Angiogenesis, 2004)

An improvement of the mass flux convection parameterization scheme and its sensitivity tests for seasonal prediction over China - Ping Fan; Gao Shouting; Wang Huijun (Advances in Atmospheric Sciences, 2003)

EurΩconference Angiogenesis II - Judy R. van Beijnum; Tai-Ping D. Fan; Arjan W. Griffioen (Angiogenesis, 2003)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)

A Comparative Study of the Numerical Simulation of the 1998 Summer Flood in China by Two Kinds of Cumulus Convective Parameterized Methods - Fan Ping; Shouting Gao; Huijun Wang (Advances in Atmospheric Sciences, 2003)

Oxidative modification of lipoproteins in hypertriglyceridemic patients and hypercholesterolemic rabbits in vivo - Bing W. Liu; Yu Jiang; Ming D. Fu; Yu Liu; Ping Fan (Molecular and Cellular Biochemistry, 2000)

The effects of spaceflight on soluble protein, isoperoxidase, and genomic DNA in ural licorice (Glycyrrhiza uralensis fisch.) - Wen-Yuan Gao; Rong-Zhao Fu; Lei Fan; Shu-Ping Zhao; Kee-Yoeup Paek (Journal of Plant Biology, 2000)

From the Editor's desk - Tai-Ping Fan (Angiogenesis, 1999)

Merger of Angiogenesis and Angiogenesis Research – heading for a quality journal - Arjan W. Griffioen; Tai-Ping D. Fan (Angiogenesis, 1998)

From the Editor's Desk - Tai-Ping Fan (Angiogenesis, 1998)

Quantification of the repair process involved in the repair of a cell monolayer using an in vitro model of mechanical injury - Heather Lauder; Emma E. Frost; C. Robin Hiley; Tai-Ping D. Fan (Angiogenesis, 1998)

EDITOR-IN-CHIEF - Tai-Ping Fan (Angiogenesis, 1997)

From the Editor's Desk - Tai-Ping Fan (Angiogenesis, 1997)

Observations on the treatment of natural haemosporidia infections by total alkaloid ofPeganum harmala L. in cattle - Tingjun Hu; Bingtang Fan; Jilan Liang; Sixi Zhao; Ping Dang; Fang Gao; Mingxian Dong (Tropical Animal Health and Production, 1997)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)

From the Editor's Desk - Tai-Ping Fan (Angiogenesis, 1997)